Replacing maize grain with self-fermented agro-waste in total mixed ration improves fatty acid profile, oxidative stability and meat quality traits in goats - Rajat Bagdas; Gauri Jairath; Varun; Suman Bishnoi; Yashavanth Basavapatna Subbanna; Gorakh Mal; Ashim K. Biswas; Triveni Dutt; Arup Ratan Sen; Randhir Singh Bhatt; Lalit Kumar Soni; Birbal Singh; et al. (Meat Science, 2026)

Targeting the extracellular matrix in precision medicine: opportunities for diagnostics and therapeutics - Kanaka Durga Devi Nelluri; K. N. V. Chenchu Lakshmi; Minakshi Kommoju; Bhavana Alaparthi; Anil Kumar Kakani; P. Sai Rohith; N. Vineela Nirmala (Molecular Biology Reports, 2026)

Partial substitution of herbicides with sorghum allelopathic extract and its impact on productivity of wheat and soil microbes - Devi Lal Kikraliya; U. N. Shukla; Krishna Saharan; A. K. Meena; Moola Ram; R. C. Meena (Brazilian Journal of Microbiology, 2026)

Metabolic diversity and antioxidant activities: A comparative analysis of cultivated Juniperus communis clones - Antim K. Maurya; Kanika Devi; Vijai K. Agnihotri (Food Chemistry, 2026)

Sustainable activated carbon derived from Cyanthillium cinereum biomass for efficient adsorption of methylene blue and eosin yellow - K. Shakitha; V. N. Meena Devi (Biodegradation, 2026)

Nutritional profile and ethnomedicinal significance of wild edible fruits (WEFs) of Manipur, India - Mayanglambam Bidyalakshmi Devi; Gisandu K. Malunguja; Ashalata Devi (Next Research, 2026)

Performance Evaluation of EOS-06 OCM-3 Chlorophyll-a Retrievals in Case-1 Waters - Chiranjivi Jayaram; Neethu Chacko; Rajdeep Roy; T. Devi Varaprasada Rao; P. V. Nagamani; T. V. S. Udaya Bhaskar; K. N. Babu; Prakash Chauhan (Journal of the Indian Society of Remote Sensing, 2026)

Assessment of bioactive compounds, antioxidant pigments and mineral diversity in leaves of amaranth (Amaranthus spp.) genotypes - Ajay Kumar Sharma; Vidya Sagar; Jyoti Devi; S. V. Dwivedi; Neetu; Vishal Chugh; Ashutosh Rai; Anurag; Nakul Gupta; Rajesh Kumar; N. Rai; T. K. Behera (Genetic Resources and Crop Evolution, 2026)

Imported Cutaneous Leishmaniasis in India: Diagnosis and Treatment with Implications for Kala Azar Elimination - P. A. Fathima; Manisha Venu; Harish Kumar Shah; K. Devi; Ambooken Betsy; Abdul Salam Sarin; Manju Rahi; Prasanta Saini (Current Microbiology, 2026)

Evaluation of Shatpada Fruit Fly Traps Versus Conventional Fruit Fly Traps in Citrus in India - Sandeep Singh; Srinivas Reddy; Ranjit Kadu; Y. V. Ingle; Sikha Deka; Raaj Kumar Kokoti; L. Ranjith Kumar; Aayush Kaushal; Deepa Bhagat; S. Priya Devi; Guranshpaul Singh; Ashok Kumar; et al. (Applied Fruit Science, 2026)

Metabologenomic approach to discover aromatic polyketides, angucycline antimicrobial compounds produced by alkaliphilic Streptomyces - Shalini Devi S.; Sreenivasulu Y.; Prakruti K. (Natural Product Research, 2026)

Planthopper-induced vulnerability: amplifying fall armyworm, Spodoptera frugiperda (J.E. Smith) preference in rice - V. Chinna Babu Naik; S. Rakhesh; D. Devi Pratyusha; K. A. V. Sindhura; Kokkula Akhilesh; K. Vani Sree; R. M. Sundaram (Phytoparasitica, 2026)

Ethnobotanical inventory and therapeutic applications of medicinal plants used by tribal communities of Chintapalle Mandal, Southern Eastern Ghats, India - K. Gowri Devi; Madhulika Singh; G. Jaya Babu; Sunil K. Singh (Vegetos, 2026)

Advanced Photocatalytic Decomposition Using TiO₂ Nanorods: Optimization Through Factorial Modeling - S. K. Thiyakarajan; S. Vijayakumar; B. Akash; D. Devadharshini; V. Devi Rajeswari; V. Yamini (Nanotechnology for Environmental Engineering, 2026)

Application of bioencapsulated microalgae in marine cladoceran (Penilia sp.) for enhancing growth and improve production of Asian seabass (Lates calcarifer) - K. Nanthini Devi; P. Santhanam; A. Shenbaga Devi; P. Raju; R. Sagaya Princy; K. Rajagopal; I. S. Bright Singh; A. S. Sahul Hameed; A. Jishnu Panamoly; P. Perumal (Journal of Applied Phycology, 2026)

Characterization of Genetic Diversity in Amaranthus Species Using Morpho-Molecular Markers - Ajay Kumar Sharma; Vidya Sagar; S. V. Dwivedi; Jyoti Devi; Neetu; Shailesh K. Tiwari; Sunil K. Singh; N. Rai; Rajesh Kumar; T. K. Behera (Indian Journal of Genetics and Plant Breeding, 2026)

Unveiling the prevalence, pathogenic and molecular characterization of Xanthomonas strains responsible for bacterial leaf spot of tomato and pepper in India - P. Lokesh Babu; V. Devappa; J. Rajender; Neelam Geat; R. S. Devi; Rahul Patidar; Ainmisha Singh; V. K. Banarwal; Jasdeep Chatrath Padaria; Anju Kamra; Dinesh Singh (Journal of Plant Pathology, 2026)

Interpretable deep learning reveals spatiotemporal MRI features of brain aging that align with neurodegeneration - Nikhil N. Chaudhari; Owen M. Vega; Phoebe Imms; Jaron M. Kawamura; Nahian F. Chowdhury; Tamara Jafar; Andrei Irimia; Michael Weiner; Paul Aisen; Ronald Petersen; Clifford R. Jack; William Jagust; et al. (GeroScience, 2026)
Cortical thinning and atrophy are hallmarks of brain aging that have been characterized using magnetic resonance imaging (MRI). Brain aging involves many neuroanatomic features whose effects on brain structure remain unexplored. To address this challenge, we trained interpretable deep neural networks (DNNs) to estimate brain age (BA) from T 1 -weighted ( T 1 w) MRI. By identifying MRI features unapparent to humans, DNNs can find aging-related structural alterations above and beyond cortical thickness and atrophy. Using a novel approach to DNN interpretability, we mapped brain aging progression in 25,539 cognitively normal UK Biobank adults aged 45–83 years. Cortical aging is found to involve anatomic features becoming prominent during the 50s within frontolateral, mesolimbic, cuneal, and occipitotemporal regions. From these foci, aging-related features propagate to adjacent areas at rates peaking in the 60s. Cortical thinning and atrophy do not trend closely with neurodegeneration, but important DNN-identifiable anatomic features have spatiotemporal dynamics that match those of amyloid or tau. Our results challenge the assumption that MRI cannot map anatomic features trending with neurodegeneration. Interpretable DNNs can empower MRI to quantify anatomic aging as a process of spatial feature expansion from focal regions into nearby structures in the sequence of neurodegenerative pathology. Traditional morphometrics explain only ∼1% of variance in DNN-identifiable features, which clarifies why the former are insensitive to anatomic changes involving neurodegeneration. Our results conceptualize brain aging in the context of spatial and temporal parallels between anatomic senescence and neuropathology. These findings may help to map cognitively normal adults’ neurodegenerative anatomy even without PET measurements. Graphical Abstract

Water Mimosa var. CAU-Ekaithabi: An agronomically superior, nutrient-dense, bioactive-rich aquatic vegetable with emerging potential in functional foods - Shravan Manbhar Haldhar; Indira Sarangthem; Lokesh Kumar Mishra; N. Brajendra Singh; H. Nanita Devi; Jagan Singh Gora; Mukesh K. Berwal (Food Chemistry, 2026)

Integrated subsurface drip fertigation and residue management enhance maize resource-use efficiency in semi-arid agro-ecosystems - Arjun Singh; Anchal Dass; S. Sudhishri; V.K. Singh; Prameela Krishnan; Pravin K. Upadhyay; K. Shekhawat; R.N. Sahoo; S.S. Rathore; Ayekpam Dollina Devi; A.R. Devika (Field Crops Research, 2026)

Utilization of crop wild relatives in genetic improvement of bitter gourd, Momordica charantia L. - S. Devi; R. Neelavathi; C. Indu Rani; R. Kalaiyarasi; K. Gurusamy (Genetic Resources and Crop Evolution, 2026)

Pliocene otoliths from NW India reveal first fossil osphronemid and structure of a Himalayan freshwater ecosystem - Ningthoujam Premjit Singh; Chien-Hsiang Lin; Ramesh Kumar Sehgal; Abhishek Pratap Singh; Konsam Nildy Devi; Rigzen Angmo; Haroon Nazir; Rajeev Patnaik; K. Milankumar Sharma (Palaeobiodiversity and Palaeoenvironments, 2026)
The Neogene Siwalik deposits have long been recognised for their rich terrestrial fossil record, yet their freshwater ichthyofauna remains virtually unknown. This gap limits our understanding of past aquatic ecosystems and the biogeographic history of South Asian freshwater fishes. In this study, we report the first fossil record of freshwater fish otoliths from the Upper Siwalik Pliocene deposits of Mohand, Saharanpur district, in the northwestern Himalaya, India. Three taxa Channa (Channidae), Trichogaster fasciata (Osphronemidae), and Gobiidae indet. were discovered through our extensive bulk sampling. Among these, T. fasciata represents the second known fossil record of Osphronemidae globally and the first based on otoliths. The assemblage reflects a structured trophic composition composed of mid-level preys and apex predators. These faunal components suggest a calm, possibly lentic freshwater habitat with dense vegetation, consistent with the spawning behaviour of labyrinth fishes and the hunting of snakeheads. Despite the limited number of otoliths, this collection provides rare but significant insights into Pliocene freshwater biodiversity in the Himalayan region.

Tail-raising and head-turning as predictive behavioural indicators of calving in Murrah buffaloes - Deepak Chopra; Arun Kumar Misra; T. K. Mohanty; Rubina K. Baithalu; Indu Devi; Chinmayee Sahu; Simran Kamboj; Birender Singh; Pratibha Jareda; Prachi Chandrakar (Tropical Animal Health and Production, 2026)

Subsurface drip fertigation optimizes nitrogen distribution in soil under maize cultivation - Arjun Singh; Anchal Dass; Susama Sudhishri; V. K. Singh; R. N. Sahoo; Kapila Shekhawat; Pravin K. Upadhyay; S. S. Rathore; Ayekpam Dollina Devi (Plant and Soil, 2026)

Validation of OCM3 Operational Products Along the Coastal Waters of Southern Bay of Bengal Using In-Situ Measurements and Statistical Analysis - V. Niranjana; RM. Narayanan; P. V. Nagamani; Arvind Sahay; K. Mohammed Suhail; Thumu Devi Vara Prasad Rao; AR. Vijayalakshmi; K. N. Babu (Journal of the Indian Society of Remote Sensing, 2026)

Glycine Betaine Application as a Strategic Shield against Cadmium Toxicity by Enhancing Stress Tolerance Mechanism in Vigna radiata L. Seedlings - Gayatri Devi Biswal; D. K. Patel; Madhulika Singh (Journal of Soil Science and Plant Nutrition, 2026)

Unravelling the role of soil enzymatic activity as a vital bioindicator of soil health and fertility in agricultural systems - Ingudam Bhupenchandra; L. Devarishi Sharma; Menaka Devi Salam; Sumit Kumar; S.K. Chongtham; Anil K. Choudhary; H. Lembisana Devi; Soibam Sinyorita; Pranab Dutta; Ali Chenari Bouket; Tatiana Minkina; Chetan Keswani (Applied Soil Ecology, 2026)

Sex and APOE genotype specific brain regional vulnerability to Alzheimer's Disease - Qi Zeng; Minghui Wang; Erming Wang; Xianxiao Zhou; Peng Xu; Vahram Haroutunian; Dongming Cai; Bin Zhang; Michael Weiner; Paul Aisen; Ronald Petersen; Clifford R. Jack; et al. (GeroScience, 2026)
Alzheimer’s disease (AD) disproportionately affects women and carriers of the apolipoprotein E ε4 allele (APOE4), yet little is known about how sex and APOE interact to influence white matter (WM) integrity during disease progression. We integrated diffusion MRI and matched blood transcriptomic data to investigate these interactions and their underlying biological mechanisms. WM microstructure was quantified using diffusion tensor imaging (DTI) and neurite orientation dispersion and density imaging (NODDI), and regional vulnerability was assessed with a composite vulnerability score (CVS) derived from associations between diffusion features and AD severity across clinical traits in each of the four sex-APOE groups (female or male, with or without APOE4). Brain parcellation with the Eve atlas revealed regions consistently affected across sex-APOE groups (e.g., parahippocampal and superior temporal gyri) and regions specific to individual groups (e.g., the cingulum in females with APOE4 and the middle frontal gyrus in males without APOE4). Gene co-expression network analysis of the matched blood expression data identified gene subnetworks linked to group-specific regional vulnerability, including a muscle tissue morphogenesis module regulated by NEURL1B and HIST1H2BN associated with middle frontal gyrus vulnerability. These findings demonstrate that sex and APOE genotype jointly shape region-specific WM vulnerability and its molecular signatures in AD. Understanding these interactions provides novel mechanistic insights and may inform precision approaches to drug development, biomarker discovery, and clinical trial design for AD.

Simultaneous removal of Hg2 + , Pb2+, Mn2+, and Fe2+ ions from water by arsiron nilogon with modified doses: Laboratory to field experience - Shamiran Baroi; Anup J. Bora; Saranga Baishya; Tushmita Das; Rituparna Saikia; Anwesha Chaliha; Priya Devi; Robin K. Dutta (Process Safety and Environmental Protection, 2026)

Nirmala indices bridge molecular connectivity and genetic stability: A graph-theoretic lens on purines and pyrimidines - Nalini Devi K.; Srinivasa G. (BioSystems, 2026)

In silico analysis of Barleria cuspidata compounds against Streptococcus mutans biofilm-associated proteins - E. Gaayathiri Devi; M. K. Nisha (In Silico Pharmacology, 2026)

Regional variation in serum ficolin levels and their association with disease activity and clinical manifestations in systemic lupus erythematosus (SLE) patients from India - Kirti Rai; Ridi Khatri; Amrutha Jose; Deepak Upadhaya; Sukham Rishikanta Singh; Kyntiewdor Lyting; Husulu; Harshada Konkar; Prashant Tapase; Milind Nadkar; Anjali Rajadhyaksha; Pooja Jaiswal; et al. (Immunologic Research, 2026)

Conservation agriculture for riverine agri-food systems under the climate crisis: enhancing soil health and mitigating erosion - Pazhanisamy S.; Devendra Singh; Rodda Chandana Devi; Vijay Singh Meena; Sunil Kumar; R.S. Singh; S.S. Prasad; R. Sushma Devi; Jogdande Sai Prasad; K. Damodar; Abhinandan Singh; V. Sridevi; et al. (Soil and Tillage Research, 2026)

Anti-arthritic potential of Cassia fistula leaf extracts and sennoside B via NF-κB inhibition: In vivo and in vitro pre-clinical study - Aashcharya U. Mishra; Sumati Sen; Meenu Devi; Abhishek K. Rai; Ratnasekhar Ch; Dnyaneshwar U. Bawankule; Daya N. Mani (Inflammopharmacology, 2026)

Exploring the microbial basis of postbiotic and paraprobiotic therapy in ulcerative colitis - N. Pavithra; M. Devi; S. Nirenjen; B. Keerthana; V. K. Giresh kumar; R. Yogalakshmi; M. G. Priyadharshni; N. Harikrishnan (Archives of Microbiology, 2026)

Simultaneous removal of Hg(II), Pb(II), Ni(II), Cd(II), Cu(II), Mn(II), Fe(II), ions and fluoride from groundwater by Fluoride Nilogon: Phosphoric acid-crushed limestone treatment (PACLT) - Tushmita Das; Saranga Baishya; Shamiran Baroi; Priya Devi; Priyanka Ray; Rituparna Saikia; Robin K. Dutta (Journal of Water Process Engineering, 2025)

Sulphated polysaccharides and biomaterials: Steering stem cell fate - Deepika Bhat. K; Yashaswini Devi G.V.; Joel Rimson Pinto; Bipasha Bose; Sudheer Shenoy P. (Carbohydrate Polymers, 2025)

Spectral bounds for Sombor and Sombor energy indices: A graph-theoretic study of neurotransmitter molecular networks - Nalini Devi K.; Srinivasa G. (BioSystems, 2025)

Comparative Flood Risk Mapping Using Knowledge-Driven, Data-Driven, and Ensemble Models in a Humid Tropical River Basin in India - Chandini Padmanabha Panicker Chandr Senan; Rajendran Shobha Ajin; B. R. Anaswara Devi; A. Rajaneesh; Jitendra K. Nagar; K. S. Sajinkumar (Water Conservation Science and Engineering, 2025)

Harnessing IDO inhibitors to optimize cancer immunotherapy - Safia Obaidur Rab; Huda K. Jaafar; Majid S. Jabir; H. Malathi; Seema Devi; Atreyi Pramanik; Hussein Riyadh Abdul Kareem Al-Hetty; Mohammed Jawad Alnajar; Sabrean F. Jawad; Yasser Fakri Mustafa (Naunyn-Schmiedeberg's Archives of Pharmacology, 2025)

Transmission dynamics and localization of tomato leaf curl New Delhi virus in cucurbits via sweet potato whitefly, Bemisia tabaci (Gennadius) - Kathiresan Sivagnanapazham; Gandhi Karthikeyan; Shanmugasundram Pavithran; Sankarasubramanian Harish; Marimuthu Murugan; T. K. S. Latha; Harinarayanan Usha Nandhini Devi (Molecular Biology Reports, 2025)

Unlocking the Potential of Arbuscular Mycorrhizal Fungi: Exploring Role in Plant Growth Promotion, Nutrient Uptake Mechanisms, Biotic Stress Alleviation, and Sustaining Agricultural Production Systems - Ingudam Bhupenchandra; Sunil Kumar Chongtham; Ayam Gangarani Devi; Pranab Dutta; Manas Ranjan Sahoo; Sansuta Mohanty; Sumit Kumar; Anil K. Choudhary; Elangbam Lamalakshmi Devi; Soibam Sinyorita; Soibam Helena Devi; M. Mahanta; et al. (Journal of Plant Growth Regulation, 2025)

Identification and functional characterization of a cold-inducible UDP-Glycosyltransferase (GgUGT72L11) from Glycyrrhiza glabra - Shahnawaz Hussain; Bhawna Verma; Malik Muzafar Manzoor; Pooja Goyal; Ritu Devi; Ajai P. Gupta; Manoj K. Dhar; Shakti Kumar Dhiman; Fariha Chowdhary; Debaraj Mukherjee; Suphla Gupta (Journal of Plant Biochemistry and Biotechnology, 2025)

Towards sustainable management: growth and population assessment of the deep-sea shrimp Aristeus alcocki Ramadan, 1938, in Southwestern Indian waters - Rekha Devi Chakraborty; Gayathri A. P; Gyanaranjan Dash; G. Maheswarudu; Josileen Jose; P. Laxmilatha; A. P. Dineshbabu; Eldho Varghees; Somy Kuriakose; T. M. Najmudeen; L. Sreesanth; N. Ragesh; et al. (Journal of Coastal Conservation, 2025)

LPCAT3—dependent remodeling of the phospholipids and lipid rafts is essential for vascular proinflammatory signaling and the development of atherosclerosis - Vijay Kondreddy; Jhansi Magisetty; Pranshuta Rawat; Muralidharan Kathirvel; Ramchandra Reddy Jala; B. L. A. Prabhavathi Devi; Sunil K. Singh (Inflammation Research, 2025)

Genomics-assisted stacking of waxy1, opaque2, and crtRB1 genes for enhancing amylopectin in biofortified maize for industrial utilization and nutritional security - Subhra J. Mishra; Firoz Hossain; Rajkumar U. Zunjare; Rashmi Chhabra; Ashvinkumar Katral; Ikkurti Gopinath; Vinay Bhatt; Govinda Rai Sarma; Zahirul A. Talukder; Ravindra K. Kasana; Elangbam L. Devi; Konsam Sarika; et al. (Functional & Integrative Genomics, 2025)

Cognitive neurodynamic approaches to adaptive signal processing in wireless sensor networks - K. G. Shanthi; A. Mary Joy Kinol; S. Rukmani Devi; K. Kannan (Cognitive Neurodynamics, 2025)

Accelerated development of MTL and DMP gene-based subtropically-adapted maternal haploid inducer lines in maize using molecular breeding - Nisrita Gain; Vignesh Muthusamy; Rashmi Chhabra; Amitkumar D. Kyada; Suman Dutta; Gulab Chand; Ravindra K. Kasana; Konsam Sarika; Elangbam L. Devi; Jayanthi Madhavan; Rajkumar Subramani; Rajkumar U. Zunjare; et al. (Planta, 2025)

Exploring the genetic potential of cultivated genepool of okra from National Genebank, India - A. Suma; K. Joseph John; M. Latha; P. P. Thirumalaisamy; K. Venkatesan; P. Neeraja; P. P. Gopinath; K. K. Gangopadhyay; Chithra Devi Pandey; Sushil Pandey; P. K. Singh; G. P. Singh (Genetic Resources and Crop Evolution, 2025)

Isolation and characterization of xyloglucan endotransglucosylase/hydrolase (XET/XTH) provide insights on the functional evolution of XET family proteins in ginger (Zingiber officinale Roscoe) - Arshya Devi; Divya P. Syamaladevi; B. Mekha; K. S. Nehamol; I. P. Vijesh Kumar; T. E. Sheeja; D. Prasad (Genetic Resources and Crop Evolution, 2025)

Possible contribution of ground motion to modify ionosphere before the 2011 Tohoku-Oki Mw9.1 earthquake - C.H. Chen; Y.Y. Sun; K.-I. Oyama; M. Devi (Advances in Space Research, 2025)

Identification of pod borer resistant pigeonpea: an introgression breeding with Cajanus scarabaeoides accompanied by integrated screening - G. K. Sujayanand; Sachin Dubey; Dibendu Datta; Satheesh Naik; Kalpana Tewari; Anup Chandra; Rinki Devi; Prabhu Govindasamy; G. P. Dixit (Arthropod-Plant Interactions, 2025)

Youngest Toba Tuff (YTT) beds as a Late Pleistocene isochron in the Indian subcontinent? New geochronological and sedimentological insights - Devara Anil; Monika Devi; Prabhin Sukumaran; B. V. Lakshmi; K. Deenadayalan; Sunil Kumar; Ambili Anoop; Zakir Khan; Vrushab Mahesh; Gopesh Jha; P. Ajithprasad; Naveen Chauhan (Journal of Quaternary Science, 2025)
The ~75 ka Young Toba super‐eruption was a catastrophic extreme event that spewed vast quantities of volcanic ash and aerosols and is argued to have caused a drastic volcanic winter, climatic upheaval, and a human genetic bottleneck. The global and regional impacts of the eruption on climate dynamics and past hominin populations are strongly contested due to conflicting global climatic records and archeological datasets. The Indian subcontinent is a key place for Toba research due to its proximity to Mt. Toba (Indonesia). Most of central and peninsular India is estimated to have been covered by a ~5 cm ash layer, with deposits found in different fluvial systems across the subcontinent. For a long time, many of these Youngest Toba Tuff (YTT) deposits, occurring in both archeological and non‐archeological contexts, were believed to be primary tephra deposits dating to ~75 ka. However, the use of YTT as a Late Pleistocene chronological marker is surrounded by many uncertainties, primarily due to the complex and varying nature of the depositional and sedimentary contexts of YTT and chronological irregularities. Recent sedimentological and geochronological data indicate that most of the YTT deposits in India are secondary deposits, resulting from later erosion and redeposition occurring thousands of years after the eruption. This highlights the unreliability of YTT as an isochron and raises questions about the credibility of paleoclimate (terrestrial and marine) and archeological datasets that use YTT as a chronological marker. Our study contributes to this debate and reveals the complex redepositional history of YTT deposits in the Indian subcontinent through geochronological and geoarchaeological analyses of YTT‐bearing sequences from Motravulapadu, Andhra Pradesh, India. Our findings suggest that the final burial of YTT occurred around 30 ka, highlighting a temporal gap of more than 40 000 years after the eruption. Notably, the redeposited tephra horizon appears visually uniform and compositionally pure, despite its secondary context, adding complexity to its stratigraphic interpretation. Our multiproxy sedimentological approach demonstrates the importance of integrating detailed stratigraphic, magnetic, granulometric, and chronological analyses to resolve such depositional ambiguities; it underscores the need for similar frameworks in future studies of YTT‐bearing sequences. We suggest that YTT in India cannot be used as a reliable chronological marker without independent age estimations of its deposition. However, it has significant potential for identifying regional geological events.

Three-dimensional crustal resistivity image of the central Indian tectonic zone, India: derived from magnetotelluric studies - Anita Devi; Prasanta K. Patro; K.K. Abdul Azeez (Journal of Asian Earth Sciences, 2025)

Glycine betaine mitigates cadmium toxicity in plants via redox homeostasis and osmotic adjustment - Gayatri Devi Biswal; Madhulika Singh; D. K. Patel; Sheo Mohan Prasad (Journal of Plant Biochemistry and Biotechnology, 2025)

Assessment of the incidence and severity of foliar fungal diseases in black aromatic rice - Bijeeta Thangjam; Ph Sobita Devi; Bireswar Sinha; Kota Chakrapani; W Tampakleima Chanu; K SardaDevi; Y Premika Devi; Tusi Chakma; LNK Singh; Th Renuka Devi; N Gopimohon Singh (Vegetos, 2025)

Clinical spectrum of AES (Acute encephalitis syndrome) and a syndromic approach for its diagnosis - Sidharth S; Sarada Devi K L; Sreelatha K H (Journal of NeuroVirology, 2025)

Correction: Meeting forest product needs through agroforestry: insights from rural mid-hills of Western Nepal - Namrata Devi Khatri; Suman Ghimire; Suman K. C. (Agroforestry Systems, 2025)

Agro-industrial waste management: solid-state fermentation for biomass conversion and valorisation to value-added products - Moinal Hoque; K. T. Ramya Devi (Systems Microbiology and Biomanufacturing, 2025)

Phosphate-solubilizing microorganisms for sustainable phosphorus management in rice - S. Ahash; K. Manikandan; T. Sivasankari Devi; S. Elamathi; S. Maragatham; K. Subrahmaniyan (Rhizosphere, 2025)

Variations in mantle flow beneath the Eastern Himalaya inferred from shear wave splitting - Arti Devi; Sunil K. Roy; Jyotima Kanaujia; Venkatesh Vempati; M. Ravi Kumar (Physics of the Earth and Planetary Interiors, 2025)

Cassia fistula fruit pulp extracts mitigate collagen-induced arthritis via regulation of oxidative stress and inflammation - Aashcharya U. Mishra; Sumati Sen; Mridula Sahu; Meenu Devi; Dewasya P. Singh; Aakriti Gupta; Abhishek K. Rai; Ratnasekhar Ch; Ashutosh K. Shukla; Dnyaneshwar U. Bawankule; Daya N. Mani (Inflammopharmacology, 2025)

Production and Extraction of Red Bioactive Pigment from Streptomyces griseorubiginosus and Formulation of Bio-Lip Balm - S. Vignesh; P. M. Anandu; G. S. Gopuraj Varrier; Nikhil Brijmohan; G. Gokula Krishnan; Sanjeev K. Ganesh; Sreelakshmi R. Nair; V. Mohanasrinivasan; C. Subathra Devi (Indian Journal of Microbiology, 2025)

Meeting forest product needs through agroforestry: insights from rural mid-hills of Western Nepal - Namrata Devi Khatri; Suman Ghimire; Suman K. C. (Agroforestry Systems, 2025)

Metabolite profiling and wound healing potential of Gynura cusimbua in zebrafish model - Anuradha Moirangthem; Shandyarani Devi Laishram; Sonia Sougrakpam; Sushma Khuraijam; Sharmila Laishram; Sushil K. Chaudhary; Sachin Jorvekar; Roshan M. Borkar; Pulok K. Mukherjee; Nanaocha Sharma (Advances in Traditional Medicine, 2025)

Imidazopyridine Based Fluorescent Turn-Off Sensor for Selective Recognition of Fe3+ Ions and its Application in Test Strips - Akanksha Manhas; Sonakshi Sasan; Lalita Devi; Manu Sharma; Avtar Changotra; Pawan Kumar; Kamal K. Kapoor (Journal of Fluorescence, 2025)

Preface: Advancing deep learning for remote sensing time series data analysis - Hankui K. Zhang; Gustau Camps-Valls; Shunlin Liang; Devis Tuia; Charlotte Pelletier; Zhe Zhu (Remote Sensing of Environment, 2025)

Predicting the progression of MCI and Alzheimer’s disease on structural brain integrity and other features with machine learning - Marthe Mieling; Mushfa Yousuf; Nico Bunzeck; Michael Weiner; Paul Aisen; Ronald Petersen; Clifford R. Jack; William Jagust; Susan Landau; Monica Rivera-Mindt; Leslie M. Shaw; Edward B. Lee; et al. (GeroScience, 2025)
Machine learning (ML) on structural MRI data shows high potential for classifying Alzheimer’s disease (AD) progression, but the specific contribution of brain regions, demographics, and proteinopathy remains unclear. Using Alzheimer’s Disease Neuroimaging Initiative (ADNI) data, we applied an extreme gradient-boosting algorithm and SHAP (SHapley Additive exPlanations) values to classify cognitively normal (CN) older adults, those with mild cognitive impairment (MCI) and AD dementia patients. Features included structural MRI, CSF status, demographics, and genetic data. Analyses comprised one cross-sectional multi-class classification (CN vs. MCI vs. AD dementia, n = 568) and two longitudinal binary-class classifications (CN-to-MCI converters vs. CN stable, n = 92; MCI-to-AD converters vs. MCI stable, n = 378). All classifications achieved 70–77% accuracy and 61–83% precision. Key features were CSF status, hippocampal volume, entorhinal thickness, and amygdala volume, with a clear dissociation: hippocampal properties contributed to the conversion to MCI, while the entorhinal cortex characterized the conversion to AD dementia. The findings highlight explainable, trajectory-specific insights into AD progression.

Unveiling the interaction, cytotoxicity and antibacterial potential of pyridine derivatives: an experimental and theoretical approach with bovine serum albumin - Rosalin Das; Patitapaban Mohanty; Pragyan P. Dash; Swagatika Mishra; Ajit K. Bishoyi; Lokanath Mishra; Laxmipriya Prusty; Devi P. Behera; Debasmita Dubey; Monalisa Mishra; Harekrushna Sahoo; Mohd S. Khan; et al. (Naunyn-Schmiedeberg's Archives of Pharmacology, 2025)

Single-quad gas chromatography estimation of a few selected pesticides as residues in spices of the National Capital Region of Delhi - Okram Zenita Devi; Sudeep Mishra; Samsul Alam; L. K. Thakur (Environmental Monitoring and Assessment, 2025)

Photocatalytic advancements and applications of titanium dioxide (TiO₂): Progress in biomedical, environmental, and energy sustainability - Karuppiah Nagaraj; Suriyan Radha; Christy G Deepa; K. Raja; Vanitha Umapathy; Nilesh Prakash Badgujar; Nikhil M Parekh; Thangavel Manimegalai; Lakshmanan Archana Devi; Chandrabose Uthra (Next Research, 2025)

Nanoplastics in heat-sensitive food packaging: A review of migration, detection, health, and environmental impacts - Senthilkumar Palanisamy; Barani Kumar Saravana Kumar; Aishwarya Vetrivel; Rahul Jacob Michael; Nivethitha Babu; Sanjay Sharan Nallamuthu; Kokila Saravanan; Shanmugam Venkatachalam; Naveen Kumar R J; Gayathri Devi Selvaraju; Rajendran K. Selvakesavan; Jintae Lee; et al. (Food Control, 2025)

Eco-phenological drivers of black gram (Vigna mungo (L) Hepper) productivity in diverse environments and their implications for crop improvement - Ashok K. Parihar; Kali Krishna Hazra; Amrit Lamichaney; Debjyoti Sen Gupta; Anil K. Singh; Jai Dev; Samuel Jaberson; Ajaj A. Lone; S.P. Das; Shayla Bindra; R.K. Panwar; Ashok Kumar; et al. (Field Crops Research, 2025)

Photodegradation of methylene blue from waste water under visible light and bacterial growth inhibition by GO and rGO blended CdO: Mn nanoparticles– a comparative study - N. Manjula; A. R. Balu; B. Sowmiya Devi; S. Chitra Devi; K. Devendran; M. Sriramraj; S. Adityan; A. Vinith (Nanotechnology for Environmental Engineering, 2025)

Genomic insights into drug resistance and virulence determinants in rare pyomelanin-producing clinical isolates of Acinetobacter baumannii - Lipsa Panda; Krishnapriya GK; Ajit Ramesh Sawant; Santosh Kumar Singh; Minakshi Gupta; Sheela Devi C; P Shashikala; K Prashanth (European Journal of Clinical Microbiology & Infectious Diseases, 2025)

Photocatalytic self-Fenton degradation of tetracycline over Z-scheme functionalized g-C3N4/CeO2/Bi2S3 hydrogel beads: Dynamics, mechanism, degradation pathways and toxicity analysis - K. Vijaya Suryaa; Akash Balakrishnan; Mahendra Chinthala; Khwairakpam Bidya Devi; Hritankhi Tripathy; Arvind Kumar; Tejraj M. Aminabhavi; Sami Rtimi (Chemical Engineering Journal, 2025)

Remote Sensing Analysis of the LIDAR Drone Mapping System for Detecting Damages to Buildings, Roads, and Bridges Using the Faster CNN Method - S. Meivel; K. Indira Devi; A. Sankara Subramanian; G. Kalaiarasi (Journal of the Indian Society of Remote Sensing, 2025)

Enhancing soil arsenic immobilization with organic and inorganic amendments: insights from sorption–desorption study - Md Basit Raza; Siba Prasad Datta; Debasis Golui; Mandira Barman; Prasenjit Ray; Devi Upadhyay; Rahul Mishra; Arkaprava Roy; Amit K. Dash (Environmental Monitoring and Assessment, 2024)

Unveiling primary production dynamics in the southern Bay of Bengal: Comparative analysis of in-situ measured data with multiple primary production models - Narayanan RM.; Niranjana V.; Nagamani P.V.; Arvind Sahay; Mini Raman; Sundara Vadhanan SD.; Giridharan E.; Mohammed Suhail K.; Thumu Devi Vara Prasad Rao; Y. Umamaheswara Rao; Benedict Rosario C. (Regional Studies in Marine Science, 2024)

Garcinol enriched fraction of Garcinia morella (Gaertn.) Desr. fruit rind improves gut health and reduces the risk of nonalcoholic fatty liver disease by regulating PCK1/ACC/SREBP1/FASn pathway in a mouse model - Devi Basumatary; Santanu Das; M. Bidyarani Devi; G. Shalini Devi; Pranamika Sarma; Ashis K. Mukherjee; Mojibur R. Khan; Jagat C. Borah (Food Research International, 2024)

Assessment of resistance in French bean genotypes against Meloidogyne incognita and Sclerotinia sclerotiorum - Sucherita Bains; Sukhjeet Kaur; Rupeet Gill; Ruma Devi; N. K. Dhillon (Indian Phytopathology, 2024)

Acute Respiratory Syndrome Mimicking Shipping Sickness in Theileria buffeli Infected Buffalo Calf - Varghese Raina; Y. Ajith; Sasi Adithya; S. Anandu; N. Athira; K. S. Athira; P. Preena; K. Vinodkumar; K. Mathew Manju; C. S. Mahima; Jose Akshaya; B. Bruce Alby; et al. (Acta Parasitologica, 2024)

Multifunctional electrospun membranes incorporated with metal oxide nanoparticles, cellulose acetate, and polyvinylpyrrolidone for wastewater treatment: Oil/water separation, dye adsorption, and dye degradation - Chaithra K P; Arun Varghese; Vinod T. P.; Sunaja Devi K. R. (Chemical Engineering Journal, 2024)

A multi-faceted approach involving laboratory assay, glasshouse, and field experiments in identifying stem rot (incited by Sclerotium rolfsii Sacc.) resistance in advanced breeding lines of groundnut - Manasa Ramaraju; R. Sarada Jayalakshmi Devi; K. Vemana; K. John; G. Rama Rao; Hari Kishan Sudini (Australasian Plant Pathology, 2024)

Enzyme-mediated adaptation of herbivorous insects to host phytochemicals - Showket Ahmad Dar; Wajid Hasan; Yendrembam K. Devi; Ivana Tlak Gajger; James John (Phytochemistry Reviews, 2024)

Enhancing hoof health and locomotion in crossbred dairy cows: impact of recycled manure solids bedding on lameness incidence and gait kinematics - Selladurai Praveen; Mukund A. Kataktalware; Maharajan Lavanya; Sakhare Abhijeet; Dhaarani Chinnusamy; Sakthivel Jeyakumar; Menon Rekha Ravindra; G. Letha Devi; K. P. Ramesha (Tropical Animal Health and Production, 2024)

Spatial analysis and assessment of soil erosion in the southern Western Ghats region in India - Anand B.; Remitha K.R.; Shanmathi Rekha R.; Midhuna Devi M.; Ramaswamy K. (Environmental Monitoring and Assessment, 2024)

Genetic association study of rs1801133 of MTHFR, rs4646903 of CYP1A1, null mutation of GSTM1&GSTT1 with leukemia in the Jammu region of north Indian population - Sushma Devi; Jyotdeep Kour Raina; Pawan Kumar; Amrit Sudershan; Ravi Sharma; Rakesh K. Panjalyia; Sanjeev K. Digra; Parvinder Kumar (The Nucleus, 2024)

Assessment of long-term spatio-temporal variability of hot extremes and associated physical mechanism over India - Rani Devi; K. C. Gouda; Smrutishree Lenka (Stochastic Environmental Research and Risk Assessment, 2024)

Artificial intelligence assisted identification of potential tau aggregation inhibitors: ligand- and structure-based virtual screening, in silico ADME, and molecular dynamics study - Bhanuranjan Das; Alen T. Mathew; Anurag T. K. Baidya; Bharti Devi; Rahul Rampa Salmon; Rajnish Kumar (Molecular Diversity, 2024)

Unravelling the genetic diversity of Garcinia pedunculata Roxb. with multivariate analysis - T. K. Hazarika; Lairenjam Saroja Devi; Linthoingambi Ningombam; Panthor Debbarma; Rody Ngurthankhumi (Genetic Resources and Crop Evolution, 2024)

Tailoring crystalline Mn5O8 nanostructures: Kinetic control and stabilization for enhanced electrocatalytic O2 evolution - Supriya Rana; Ahmed Belal Salik Usmani; Sapna Devi; Ritika Wadhwa; Krishna K. Yadav; Surinder.K. Mehta; Menaka Jha (Fuel, 2024)

Attention module incorporated transfer learning empowered deep learning-based models for classification of phenotypically similar tropical cattle breeds (Bos indicus) - Radhika Warhade; Indu Devi; Naseeb Singh; Shruti Arya; K. Dudi; S. S. Lathwal; Divyanshu Singh Tomar (Tropical Animal Health and Production, 2024)

Climatology of thermodynamic indices and background synoptic conditions responsible for severe convection during pre‐ to post‐monsoon seasons over Indian region - A. Madhulatha; M. Mohapatra; K. Sathi Devi; D. R. Pattanaik; M. Rajeevan; Anand Kumar Das; R. K. Jenamani; Naresh Kumar (International Journal of Climatology, 2024)
To investigate the mechanisms responsible for severe convection linked with a variety of mesoscale, synoptic systems over the Indian region, a preliminary analysis is conducted. Using IMD RSRW/Reanalysis (ERA5)/Lightning (TRMM LIS) products both local‐scale thermodynamics and large‐scale background conditions responsible for the major lightning hot spots in different seasons are investigated. In the pre‐monsoon season, high lightning activity over NE Indian region is due to moisture intrusion by south‐westerly at lower levels (warm air advection), along with mid‐level north westerlies (cold air advection) which favour the low‐level convergence and upper‐level divergence. SCS over south India are mainly attributed to wind discontinuity over the region. During monsoon season major lightning activity in NW India is due to the presence of heat low and the rest of the country less intense SCS activity is evident due to high wind shear conditions in connection with low‐level (westerly) and upper‐level (easterly jet stream). In the post‐monsoon season, major lightning in south India are due to the prevailing north‐easterlies and in north India, the activity is attributed to the passage of western disturbance (WD). Station plot analysis suggests the varied distribution of thermodynamic indices season/region‐wise due to the diverse background forcing. Correlation analysis between the lightning and thermodynamic indices suggests that more skillful indices are KI (~0.7 to 0.8), precipitable water (PPW) (~0.8) (pre‐monsoon, monsoon) and (PPW) (~0.8), convective available potential energy (CAPE) (~0.6) in post monsoon over respective lightning hot‐spot regions. Independent verification using Wyoming data/reanalysis for different case studies suggests that monitoring the monthly thresholds of highly correlated indices provides a helpful proxy to operationally forecast the severe convective systems (season/region). Mean Equivalent potential temperature, and mixing ratio in mixed layer has shown reasonable association with the lightning occurrence over all lightning hot spot regions which are implemented in the IMD GFS and IMD WRF models.

Biomanufacturing of ricinoleic acid from castor oil using immobilized lipase of Pseudomonas guariconensis as biocatalyst - Devi Rajan; Akshaya Benesh; K Madhavan Nampoothiri (Biocatalysis and Agricultural Biotechnology, 2024)

Racial diversity in Uromyces appendiculatus causing French bean rust - Banita Devi; Gurvinder Singh; Satish K. Gupta; Pramod Prasad; S. C. Bhardwaj; Vinaykumar Rachappanavar (Indian Phytopathology, 2024)

Antimicrobial and Probiotic Potential of Lactobacilli Associated with Traditional Fermented Beverages - Surmani Huidrom; Pulok K. Mukherjee; Sarangthem Indira Devi (Current Microbiology, 2024)

Integrated use of ligand and structure-based virtual screening, molecular dynamics, free energy calculation and ADME prediction for the identification of potential PTP1B inhibitors - Bharti Devi; Sumukh Satyanarayana Vasishta; Bhanuranjan Das; Anurag T. K. Baidya; Rahul Salmon Rampa; Manoj Kumar Mahapatra; Rajnish Kumar (Molecular Diversity, 2024)

Mycorrhiza in Improving Morpho-Physiological and Biochemical Parameters of Chickpea Genotypes (Cicer arietinum L.) Under Salinity Stress - Pooja Pooja; Sridevi Tallapragada; Minakshi Yadav; R. K. Chugh; Sakshi Saini; Sarita Devi (Journal of Crop Health, 2024)

Evaluating implementation of NCCN guideline-directed genetic screening recommendations for patients with pancreatic ductal adenocarcinoma - Aditya K. Ghosh; Sheena Bhushan; Oluseyi Abidoye; Shane S. Robinson; Ania Izabela Rynarzewska; Devi Sampat (Cancer Causes & Control, 2024)

Factors regulating proliferation and co-occurrence of loricate ciliates in the microzooplankton community from the eastern Arabian Sea - C. R. Asha Devi; Jhimli Mondal; N. N. S. Vishnu; C. K. Sherin; K. J. Albin; I. Anandavelu; G. V. M. Gupta (Aquatic Sciences, 2024)

Evaluating the performance of electrocoagulation system in the removal of polystyrene microplastics from water - Akhila Subair; Priya K L; Suchith Chellappan; Thamanna Rahuman A; J. Hridya; P.S. Devi; Mariyam Salkka S; M.S. Indu; Arivalagan Pugazhendhi; Chingakham Chinglenthoiba (Environmental Research, 2024)

Study of iron-based metal–organic framework for selenite removal from water - V. Sharma; P. Borah; S. S. Bhinder; S. K. Kansal; P. Devi (International Journal of Environmental Science and Technology, 2024)

Exploring the energy-climate-agriculture (ECA) nexus: a roadmap toward agricultural sustainability in Asian countries - Abbas Ali Chandio; Korhan K. Gokmenoglu; Devi Prasad Dash; Irfan Khan; Fayyaz Ahmad; Yuansheng Jiang (Environment, Development and Sustainability, 2024)

Post-violet infrared stimulated luminescence (pVIRSL) dating protocol for potassium feldspar - Monika Devi; Naveen Chauhan; Ashok K. Singhvi (Quaternary Geochronology, 2024)

Centella asiatica Leaf Extract Mediated One-Pot Green Synthesized rGO Decorated PbS/CdO Nanocomposite for Catalytic Degradation of Methyl Violet from Wastewater and Resistance Against Bacillus subtilis and Pseudomonas aeruginosa Bacterial Strains - M. Suganya; A. R. Balu; S. Chitra Devi; K. Usharani; M. Sriramraj; K. Devendran; S. Adityan (Water, Air, & Soil Pollution, 2024)

Toxicological implications of industrial effluents on plants: a review focusing on phytoremediation techniques - A. Hansa; A. Devi; M. Upadhyay; H. Gupta; K. Syam; B. Asgari Lajayer; R. Sharma (International Journal of Environmental Science and Technology, 2024)

Socio-economic sustainability with circular economy — An alternative approach - Pulok Kumar Mukherjee; Bhaskar Das; Pardeep K. Bhardwaj; Soibam Tampha; Huidrom Khelemba Singh; Leimapokpam Demi Chanu; Nanaocha Sharma; Sarangthem Indira Devi (Science of The Total Environment, 2023)

Ag decorated Zn-Al layered double hydroxide for adsorptive removal of heavy metals and antimicrobial activity: Numerical investigations, statistical analysis and kinetic studies - P.K. Asha; K. Deepak; M.K. Prashanth; L. Parashuram; V.S. Anusuya Devi; S. Archana; H. Shanavaz; S. Shashidhar; K.N. Prashanth; K. Yogesh Kumar; M.S. Raghu (Environmental Nanotechnology, Monitoring & Management, 2023)

Bourdieu’s sociological lens: unveiling the dynamics of household carbon footprint in the Kalyani sub-division of Nadia district, West Bengal, India - Madhushree Dey; Rajesh K. Gautam; Aribam Bijayasundari Devi (Environment, Development and Sustainability, 2023)

Source and depositional conditions of early Palaeogene coal-bearing sediments, Meghalaya, Eastern India - Sh Priyokumar Singh; Arka Rudra; Y Raghumani Singh; Suryendu Dutta; N Reshma Devi; A Bijayalaxmi Devi; Gyanendra K Trivedi (Journal of Earth System Science, 2023)

Tailoring the bandgap of zinc indium sulfide/boroncarbonitride heterostructure for efficient photocatalytic CO2 reduction - K. Yogesh Kumar; L. Parashuram; M.K. Prashanth; H. Shanavaz; C.B. Pradeep Kumar; V.S. Anusuya Devi; Fahd Alharethy; Byong-Hun Jeon; M.S. Raghu (Journal of Environmental Chemical Engineering, 2023)

Uniconazole improves mango flowering and fruit yield by regulating gibberellins and carbon–nitrogen nutrition - K. T. Naveena Kumara; Harminder Singh; Nirmaljit Kaur; B. K. Kang; Indira Devi (Horticulture, Environment, and Biotechnology, 2023)

Intraspecific inflorescence and palynological variations in the morphotypes of Amorphophallus paeoniifolius - Shirly Raichal Anil; A. Asha Devi; K. I. Asha; S. Suhara Beevy; E. A. Siril (Genetic Resources and Crop Evolution, 2023)

Alternate wetting and drying irrigation technology for sustainable rice (Oryza sativa) production - Kishor Mote; V. Praveen Rao; V. Ramulu; K. Avil Kumar; M. Uma Devi; T. M. Sudhakara (Paddy and Water Environment, 2023)

DNA protection ability, antihyperglycemic potential and in-vivo toxicity assessment of arrowleaf tearthumb ( Persicaria sagittata L.), a neglected aquatic plant species of Eastern Asia - Chongtham Rajiv; Subhra Saikat Roy; Thangjam Surchandra Singh; K. Tamreihao; Pintubala Kshetri; Haobijam Sanjita Devi; Susheel Kumar Sharma; Asem Kajal Devi; Pangambam Langamba; Heikham Naresh Singh; Chongtham Tania; Chongtham Sonia; et al. (Natural Product Research, 2023)

Occurrence, distribution, and toxicity assessment of polycyclic aromatic hydrocarbons in biochar, biocrude, and biogas obtained from pyrolysis of agricultural residues - Parmila Devi; Ajay K. Dalai (Bioresource Technology, 2023)

An optimal deep learning model for recognition of hidden hazardous weapons in terahertz and millimeter wave images - J. Jayachitra; Suganya Devi K; S. V. Manisekaran; Satish Kumar Satti (Earth Science Informatics, 2023)

Laccase-immobilized on superparamagnetic iron oxide nanoparticles incorporated polymeric ultrafiltration membrane for the removal of toxic pentachlorophenol - Jenet George; Abdullah K. Alanazi; P. Senthil Kumar; Swethaa Venkataraman; Devi Sri Rajendran; Jothyswarupha Krishnakumar Athilakshmi; Isita Singh; Ishani Singh; Pramit sen; Maheswari Purushothaman; Palanisamy Athiyaman Balakumaran; Vinoth Kumar Vaidyanathan; et al. (Chemosphere, 2023)

Simplified extraction protocol for plant tissues and reverse transcription RPA assay for quick and reliable diagnosis and its application in resistance screening of chilli veinal mottle virus - Huirem Chandrajini Devi; K. Sarda Devi; Rakesh Sanabam; Neeta Pathaw; Oinam Priyoda Devi; Ng. Taibangnganbi Chanu; Albert Maibam; W. Tampakleima Chanu; Jyotsana Sanasam; Subhra Saikat Roy; Ch. Premabati Devi; A. Ratankumar Singh; et al. (Crop Protection, 2023)

Mechanistic Insights into Immune-Microbiota Interactions and Preventive Role of Probiotics Against Autoimmune Diabetes Mellitus - M. Bidyarani Devi; Hridip Kumar Sarma; Ashis K. Mukherjee; Mojibur R. Khan (Probiotics and Antimicrobial Proteins, 2023)

The impact of tradable rush hour permits on peak demand: evidence from an on-campus field experiment - Kexin Geng; Devi K. Brands; Erik T. Verhoef; Yacan Wang (Transportation Research Part D: Transport and Environment, 2023)

Cost-effective, scalable production of glucose oxidase using Casuarina equisetifolia biomass and its application in the bio-Fenton oxidation process for the removal of trace organic contaminants from wastewater - Vinoth Kumar Vaidyanathan; Abdullah K. Alanazi; P. Senthil Kumar; Devi Sri Rajendran; Ashok Chidambaram; Swethaa Venkataraman; Vaithyanathan Vasanth Kumar; Gayathri Rangasamy; Hubert Cabana; Hala M. Abo-Dief (Bioresource Technology, 2023)

Advanced bioremediation by an amalgamation of nanotechnology and modern artificial intelligence for efficient restoration of crude petroleum oil-contaminated sites: a prospective study - Rupshikha Patowary; Arundhuti Devi; Ashis K. Mukherjee (Environmental Science and Pollution Research, 2023)

Assessment of nest architecture and pollination efficiency of Lasioglossum (Evylaeus) marginatum (Helictidae: Hymenoptera) - Showket A. Dar; Kounser Javeed; Laila A. Al-Shuraym; Samy Sayed; Yendrembam K. Devi; Wajid Hassan; Mohamed Morsi M. Ahmed; Naser A. Alkenani; Ivana Tlak Gajger; James John (Biologia, 2023)

The global EPTO database: Worldwide occurrences of aquatic insects - Afroditi Grigoropoulou; Suhaila Ab Hamid; Raúl Acosta; Emmanuel Olusegun Akindele; Salman A. Al‐Shami; Florian Altermatt; Giuseppe Amatulli; David G. Angeler; Francis O. Arimoro; Jukka Aroviita; Anna Astorga‐Roine; Rafael Costa Bastos; et al. (Global Ecology and Biogeography, 2023)
Motivation Aquatic insects comprise 64% of freshwater animal diversity and are widely used as bioindicators to assess water quality impairment and freshwater ecosystem health, as well as to test ecological hypotheses. Despite their importance, a comprehensive, global database of aquatic insect occurrences for mapping freshwater biodiversity in macroecological studies and applied freshwater research is missing. We aim to fill this gap and present the Global EPTO Database , which includes worldwide geo‐referenced aquatic insect occurrence records for four major taxa groups: Ephemeroptera, Plecoptera, Trichoptera and Odonata (EPTO). Main type of variables contained A total of 8,368,467 occurrence records globally, of which 8,319,689 (99%) are publicly available. The records are attributed to the corresponding drainage basin and sub‐catchment based on the Hydrography90m dataset and are accompanied by the elevation value, the freshwater ecoregion and the protection status of their location. Spatial location and grain The database covers the global extent, with 86% of the observation records having coordinates with at least four decimal digits (11.1 m precision at the equator) in the World Geodetic System 1984 (WGS84) coordinate reference system. Time period and grain Sampling years span from 1951 to 2021. Ninety‐nine percent of the records have information on the year of the observation, 95% on the year and month, while 94% have a complete date. In the case of seven sub‐datasets, exact dates can be retrieved upon communication with the data contributors. Major taxa and level of measurement Ephemeroptera, Plecoptera, Trichoptera and Odonata, standardized at the genus taxonomic level. We provide species names for 7,727,980 (93%) records without further taxonomic verification. Software format The entire tab‐separated value (.csv) database can be downloaded and visualized at https://glowabio.org/project/epto_database/ . Fifty individual datasets are also available at https://fred.igb‐berlin.de , while six datasets have restricted access. For the latter, we share metadata and the contact details of the authors.

Evaluation of anti-HMG-CoA reductase potential and simultaneous determination of phenolic compounds in hydroalcoholic extract of Ficus cunia fruits by RP-HPLC - Sushil Kumar Chaudhary; K. Chandradev Sharma; Sarangthem Indira Devi; Amit Kar; Pardeep Kumar Bhardwaj; Nanaocha Sharma; Ojit Singh Keithellakpam; Pulok K. Mukherjee (South African Journal of Botany, 2023)

Molecular and therapeutic insights of rapamycin: a multi-faceted drug from Streptomyces hygroscopicus - Sanjeev K. Ganesh; C. Subathra Devi (Molecular Biology Reports, 2023)

Correction to: Optimized adaptive neuro-fuzzy inference system based on hybrid grey wolf-bat algorithm for schizophrenia recognition from EEG signals - Kishore Balasubramanian; K. Ramya; K. Gayathri Devi (Cognitive Neurodynamics, 2023)

Current trends in management of bacterial pathogens infecting plants - Aditi Sharma; A. K. Gupta; Banita Devi (Antonie van Leeuwenhoek, 2023)

Purification, characterization and antioxidant efficacy testing of trypsin inhibitor protein from Anonna squamosa seeds - K. P. Lijith; K. Merin Rinky; D. Gayathri Devi (Journal of Plant Biochemistry and Biotechnology, 2023)

Efficacy and physical modes of EBI and strobilurin fungicides in managing French bean rust (Uromyces appendiculatus) - Gurvinder Singh; Banita Devi; S. K. Gupta; Pramod Prasad (Indian Phytopathology, 2023)

Chemical profiling and α-glucosidase inhibitory activity of essential oils extracted with two methods from some North Western Himalayan aromatic crops - Antim K. Maurya; Kanika Devi; Vijai K. Agnihotri (Natural Product Research, 2023)

Efficient removal of total arsenic (As3+/5+) from contaminated water by novel strategies mediated iron and plant extract activated waste flowers of marigold - Sudhir K. Upadhyay; Priyanka Devi; Vinay Kumar; Himanshu K. Pathak; Prasann Kumar; Vishnu D. Rajput; Padmanabh Dwivedi (Chemosphere, 2023)

A sustainable utilization of aquaculture wastewater for the production of commercially important tilapia fish and plants (mint and chickpea) in improved integrated aqua-agriculture system - A. Muhammad Alameen; K. Nanthini Devi; S. Dinesh Kumar; S. Gunabal; N. Krishnaveni; A. Gowthami; S. Sinduja; J. Roopavathy; P. Santhanam; G. Roseline Jebapriya; M. Saranya; A. Aravinth; et al. (Bioresource Technology Reports, 2023)

Chemo diversity of ginger-a potent crop in Manipur and its acetylcholinesterase (AChE) inhibitory potential - Sushil K. Chaudhary; Ojit Singh Keithellakpam; Salem Lalvenhimi; Joydeb Chanda; Shovonlal Bhowmick; Amit Kar; Bunindro Nameirakpam; Pardeep K. Bhardwaj; Nanaocha Sharma; Yallappa Rajashekar; Sarangthem Indira Devi; Pulok K. Mukherjee (Biochemical Systematics and Ecology, 2023)

Long non-coding RNAs: an overview on miRNA sponging and its co-regulation in lung cancer - Santhosh Rajakumar; Shalini Jamespaulraj; Yashesh Shah; Priyatharcini Kejamurthy; M. K. Jaganathan; Gokulnath Mahalingam; K. T. Ramya Devi (Molecular Biology Reports, 2023)

Modelling of spatial variabilities in the flow structure of a heterogeneous mangrove patch through laboratory scale models - C. A. Lekshmy Devi; P. G. Jairaj; K. Balan (Environmental Fluid Mechanics, 2023)

Optimized adaptive neuro-fuzzy inference system based on hybrid grey wolf-bat algorithm for schizophrenia recognition from EEG signals - Kishore Balasubramanian; K. Ramya; K. Gayathri Devi (Cognitive Neurodynamics, 2023)

Effect of Stocking Density on Growth, Water Quality Changes and Cost Efficiency of Butter Catfish (Ompok bimaculatus) during Seed Rearing in a Biofloc System - Snigdha S. Majhi; Soibam Khogen Singh; Pradyut Biswas; Reshmi Debbarma; Janmejay Parhi; Soibam Ngasotter; Gusheinzed Waikhom; Dharmendra Kumar Meena; Ayam Gangarani Devi; Sudhanshu S. Mahanand; K. A. Martin Xavier; Arun Bhai Patel (Fishes, 2023)
Biofloc technology is a modern-day high-density fish culture system employing heterotrophic conversion of nitrogenous waste into useful flocs for water quality control and improved welfare. However, optimization of the stocking density for the target species during seed rearing is the key to a successful farming operation. The study evaluated the effect of different stocking density on the growth, feed utilization, digestive physiology and economics in a biofloc-based seed rearing of butter catfish, O. bimaculatus. Advanced fry (1.21 ± 0.08 g) was reared in a zero-water exchange biofloc system for 90 days at stocking densities of 0.5 g/L(T1), 1.0 g/L(T2), 1.5 g/L(T3) and 2.0 g/L(T4). The observed water quality indicates a reduction in DO and pH in T4, while the total ammonia nitrogen and nitrite levels remained low in T1. Among the groups, highest weight gain was noticed in the lowest stocking density (0.5 g/L) (p

Genetic resources of sticky rice in India: status and prospects - Raj K. Gautam; Sapna Langyan; S. Vimla Devi; Rakesh Singh; D. P. Semwal; Sharik Ali; G. S. Mangat; Sutapa Sarkar; Torit Baran Bagchi; Somnath Roy; P. Senguttuvel; S. Bhuvaneswari; et al. (Genetic Resources and Crop Evolution, 2023)

Identification and characterization of genes for drought tolerance in upland rice cultivar ‘Banglami’ of North East India - Rahul K. Verma; Sanjay K. Chetia; Vinay Sharma; Kamalakshi Devi; Amarendra Kumar; Mahendra K. Modi (Molecular Biology Reports, 2022)

Growth kinetics, improved plant growth and alleviation of water stress in tomato by water stress tolerant bacteria - K. Tamreihao; Asem Kajal DevI; Pangamba Langamba; Heikham Naresh Singh; Thangjam Surchandra Singh; Chongtham Rajiv; Pintubala Kshetri; B. U. Choudhury; Susheel Kumar Sharma; Subhra Saikat Roy (Antonie van Leeuwenhoek, 2022)

Wheat yield responses to rising temperature: insights from northern plains of India - Philip Kuriachen; Asha Devi; Anu Susan Sam; Suresh Kumar; Jyoti Kumari; A. Suresh; Girish K. Jha (Theoretical and Applied Climatology, 2022)

Bacterial diversity of a floating vegetation (Phumdi) of Loktak Lake and its extracellular enzymes and bacterial antagonistic property - Jusna Nandeibam; Y Randhir Babu Singh; K Chandradev Sharma; Kh. Ranjana Devi; Pulok Kumar Mukherjee; S Indira Devi (Archives of Microbiology, 2022)

Endophytic Beauveria bassiana can protect the rice plant from sheath blight of rice caused by Rhizoctonia solani and enhance plant growth parameters - Lipa Deb; Pranab Dutta; R. K. Tombisana Devi; Dwipendra Thakuria; Dipali Majumder (Archives of Microbiology, 2022)

Fungal disease suppression and growth promotion potential of endophytic bacteria from ethnomedicinal plants - Rakhi Khunjamayum; K. Tamreihao; Roshan Singh Asem; Yurembam Rojiv Singh; Amanda Nongthombam; Khuraijam Mrinalini Devi; Thoudam Pooja Chanu; Laishram Jaya Devi; Saikat Mukherjee; Debananda S. Ningthoujam (Archives of Microbiology, 2022)

Whole genome re-sequencing of indian wheat genotypes for identification of genomic variants for grain iron and zinc content - Jitendra Kumar; Ankita Mishra; Ashish Kumar; Gazaldeep Kaur; Himanshu Sharma; Satveer Kaur; Shivani Sharma; Kirti Devi; Monika Garg; Ajay K Pandey; Mahendra Bishnoi; Ashwani Pareek; et al. (Molecular Biology Reports, 2022)

Virgin Coconut Oil (VCO) Ameliorates High Fat Diet (HFD)-Induced Obesity, Dyslipidemia and Bestows Cardiovascular Protection in Rats - Shilpa S. Shetty; P. G. Roopashree; S. V. Ramesh; Ajeet Singh; M. Arivalagan; M. R. Manikantan; Ullal Harshini Devi; K. P. Sharmila; K. B. Hebbar; N. Suchetha Kumari (Proceedings of the National Academy of Sciences, India Section B: Biological Sciences, 2022)

The profile of expression of the scaffold protein SG2NA(s) differs between cancer types and its interactome in normal vis-a-vis breast tumor tissues suggests its wide roles in regulating multiple cellular pathways - Padmini Bisoyi; Padmalaya Devi; Kusumbati Besra; Anamika Prasad; Buddhi Prakash Jain; Shyamal K. Goswami (Molecular and Cellular Biochemistry, 2022)

Upper layer characteristics of the South Eastern Arabian Sea associated with an unusual low saline pool during fag end of southwest monsoon - S Vishnu Narayanan Nampoothiri; Muhammad Shafeeque; V S Arun; B R Smitha; Kusum Komal Karati; K Rasheed; C R Asha Devi; Hashim Manjebrayakath (Journal of Earth System Science, 2022)

Mercury transportation dynamics in the Ganga Alluvial Plain, India: rainwater–groundwater–river water interaction study from hotspot region - V. Devi; M. M. Atique; A. Raju; G. Upreti; D. K. Jigyasu; J. K. Yadav; S. Singh; R. Kar; M. Singh (International Journal of Environmental Science and Technology, 2022)

Evaluation of brinjal germplasm against root-knot nematode, Meloidogyne incognita - Bharat H. Gawade; Shikha Chaturvedi; Zakaullah Khan; Chithra Devi Pandey; K. K. Gangopadhyay; S. C. Dubey; V. Celia Chalam (Indian Phytopathology, 2022)

Apomixis: A Foresight from Genetic Mechanisms to Molecular Perspectives - C. Susmita; S. P. Jeevan Kumar; Anjani Devi Chintagunta; Dinesh K. Agarwal (The Botanical Review, 2022)

Seismic velocity imaging of the Kumaon–Garhwal Himalaya, India - Prantik Mandal; D. Srinagesh; R. Vijayaraghavan; G. Suresh; B. Naresh; P. Solomon Raju; Aarti Devi; K. Swathi; Dhiraj K. Singh; D. Srinivas; Satish Saha; M. Shekar; et al. (Natural Hazards, 2022)

“Bumble bees” invitro rearing methods – a review - Harish K Sharma; Diksha Devi; Meena Thakur; Kiran Rana; Hema Prashad (International Journal of Tropical Insect Science, 2022)

Anti-viral activity of methyl 1-chloro-7-methyl-2-propyl-1h-benzo[d] imidazole-5-carboxylate against white spot syndrome virus in freshwater crab (Paratelphusa hydrodromous) - K. Karthikeyan; A. T. Manish Kumar; D. Harshini; G. Pooja; J. Arul Daniel; Pavani Yasam; G. Gracevictoria; M. Priayanka; P. Krishnaraj; R. Vidya; S. Asha Devi; Sabbasani Rajasekhara Reddy; et al. (Aquaculture International, 2022)

Quantitative Assessment and Predicting the Effects of Soil Pollutants on Herbaceous Biomass Production in Reserved Forests - Gisandu K. Malunguja; Ashalata Devi (Proceedings of the National Academy of Sciences, India Section B: Biological Sciences, 2022)

Heavy Metal Contamination of Forest Soils by Vehicular Emissions: Ecological Risks and Effects on Tree Productivity - Gisandu K. Malunguja; Bijay Thakur; Ashalata Devi (Environmental Processes, 2022)

Cover Image - Alain Maasri; Sonja C. Jähnig; Mihai C. Adamescu; Rita Adrian; Claudio Baigun; Donald J. Baird; Angelica Batista‐Morales; Núria Bonada; Lee E. Brown; Qinghua Cai; Joao V. Campos‐Silva; Viola Clausnitzer; et al. (Ecology Letters, 2022)

A global agenda for advancing freshwater biodiversity research - Alain Maasri; Sonja C. Jähnig; Mihai C. Adamescu; Rita Adrian; Claudio Baigun; Donald J. Baird; Angelica Batista‐Morales; Núria Bonada; Lee E. Brown; Qinghua Cai; Joao V. Campos‐Silva; Viola Clausnitzer; et al. (Ecology Letters, 2022)
Global freshwater biodiversity is declining dramatically, and meeting the challenges of this crisis requires bold goals and the mobilisation of substantial resources. While the reasons are varied, investments in both research and conservation of freshwater biodiversity lag far behind those in the terrestrial and marine realms. Inspired by a global consultation, we identify 15 pressing priority needs, grouped into five research areas, in an effort to support informed stewardship of freshwater biodiversity. The proposed agenda aims to advance freshwater biodiversity research globally as a critical step in improving coordinated actions towards its sustainable management and conservation.

Temperature-duration-frequency analysis over Delhi and Bengaluru city in India - Rani Devi; K. C. Gouda; S. Lenka (Theoretical and Applied Climatology, 2022)

Performance of rice (Oryza sativa (L.)) under AWD irrigation practice—A brief review - Kishor Mote; V. Praveen Rao; V. Ramulu; K. Avil Kumar; M. Uma Devi (Paddy and Water Environment, 2022)

Impact of polystyrene microplastics on major marine primary (phytoplankton) and secondary producers (copepod) - P. Raju; P. Santhanam; S. Sonai Pandian; M. Divya; A. Arunkrishnan; K. Nanthini Devi; S. Ananth; J. Roopavathy; P. Perumal (Archives of Microbiology, 2022)

Biodegradation of low-density polyethylene and polypropylene by microbes isolated from Vaigai River, Madurai, India - K. Nanthini Devi; P. Raju; P. Santhanam; S. Dinesh Kumar; N. Krishnaveni; J. Roopavathy; P. Perumal (Archives of Microbiology, 2021)

Mycobacterium tuberculosis strain lineage in mixed tribal population across India and Andaman Nicobar Island - Azger Dusthackeer; Ashok Kumar; Sucharitha Kannappan Mohanvel; B. Mahizhaveni; S. Shivakumar; S. Raghavi; S. Azhagendran; S. Vetrivel; Vikas Gangadhar Rao; Rajiv Yadav; Vijayachari Paluru; Anil Jacob Purthy; et al. (World Journal of Microbiology and Biotechnology, 2021)

Gibberellic acids promote growth and exopolysaccharide production in Tetraselmis suecica under reciprocal nitrogen concentration: an assessment on antioxidant properties and nutrient removal efficacy of immobilized iron-magnetic nanoparticles - A. Prathipa; G. Manigandan; S. Dinesh Kumar; P. Santhanam; P. Perumal; N. Krishnaveni; K. Nanthini Devi; S. Vijayalakshmi (Archives of Microbiology, 2021)

Solanum torvum mediated synthesis and characterization of silver nanoparticles for antibacterial activities - R. Renuka; K. Renuka Devi; M. Sivakami; T. Thilagavathi (Journal of Plant Biochemistry and Biotechnology, 2021)

Characterization of earthquake hazard at the Palghar and Pulichintala swarm activity regions (India) through three-dimensional modelling of b-value and fractal (correlation) dimensions - Prantik Mandal; D. Srinagesh; G. Suresh; B. Naresh; Mahalaxmi Naidu; Dhiraj Kumar Singh; K. Swathi; Arti Devi; S. Vittal; P. K. Vengala; R. Vijaya Raghavan; M. Shekar; et al. (Natural Hazards, 2021)

A new paradigm for short-range forecasting of severe weather over the Indian region - Soma Sen Roy; Pradeep Sharma; Bikram Sen; K. Sathi Devi; S. Sunitha Devi; Neetha K. Gopal; Naresh Kumar; Krishna Mishra; Shobhit Katyar; Surendra Pratap Singh; Shibin Balakrishnan; Charan Singh; et al. (Meteorology and Atmospheric Physics, 2021)

Box–Behnken design and experimental study of ciprofloxacin degradation over Ag2O/CeO2/g-C3N4 nanocomposites - D. Pinheiro; K. R. Sunaja Devi; A. Jose; K. Karthik (International Journal of Environmental Science and Technology, 2021)

Occupational exposure and challenges in tackling M. bovis at human–animal interface: a narrative review - K. Renuga Devi; L. J. Lee; Lee Tze Yan; Amin-Nordin Syafinaz; I. Rosnah; V. K. Chin (International Archives of Occupational and Environmental Health, 2021)

Impact of stochastic perturbation on the persistence and extinction risk of a multi-delayed prey–predator system in non-autonomous environment - N. S. N. V. K. Vyshnavi Devi; Debaldev Jana (Modeling Earth Systems and Environment, 2021)

Morphological and molecular characterization of new plant type core set for yield and culm strength traits in rice (Oryza sativa L.) - Rachana Bagudam; K. B. Eswari; Jyothi Badri; G. Lakshmi Devi; L. R. K. JaiVidhya; P. Bhavani; Gattu Swathi; M. Bharath; P. Raghuveer Rao; Jukanti Aravind Kumar; R. Abdul Fiyaz; C. N. Neeraja; et al. (Journal of Plant Biochemistry and Biotechnology, 2021)

Laboratory investigations on wave attenuation characteristics of Rhizophora Mucronata poir using physical models with bottom friction - C. A. Lekshmy Devi; P. G. Jairaj; K. Balan (Environmental Fluid Mechanics, 2021)

Productive and reproductive performances of two-breed and three-breed pig crosses with Niang Megha, Hampshire and Duroc inheritance reared under subtropical Eastern Himalayan hilly climate - G. Kadirvel; Y. Sovarani Devi; L. Anandakumar Singh; N. Manoranjan Singh; K. K. Baruah; B. K. Kandpal (Tropical Animal Health and Production, 2021)

Identification and characterization of a novel long juvenile resource AGS 25 - Sanjay Gupta; Giriraj Kumawat; Soniya Yadav; Rachana Tripathi; Nisha Agrawal; Shivakumar Maranna; Gyanesh K. Satpute; Gireesh Channappa; Mamta Arya; Sayed M. Husain; Virender S. Bhatia; Nanita Devi; et al. (Genetic Resources and Crop Evolution, 2021)

Newborn screening and single nucleotide variation profiling of TSHR, TPO, TG and DUOX2 candidate genes for congenital hypothyroidism - Yedukondalu Kollati; Radha Rama Devi Akella; Shaik Mohammad Naushad; Divya Borkar; Maunika Thalla; Swapna Nagalingam; Lokesh Lingappa; Rajesh K. Patel; G. Bhanuprakash Reddy; Vijaya R. Dirisala (Molecular Biology Reports, 2020)

Influence of weather patterns and air quality on ecological population dynamics of ectoparasites in goats - Y. Ajith; U. Dimri; E. Madhesh; A. Gopalakrishnan; Med Ram Verma; H. A. Samad; K. K. Reena; A. K. Chaudhary; G. Devi; J. Bosco (International Journal of Biometeorology, 2020)

Efficacy of new generation fungicides against French bean rust caused by Uromyces appendiculatus - Banita Devi; S. K. Gupta; Gurvinder Singh; Pramod Prasad (Phytoparasitica, 2020)

Designing Biomass Rice Husk Silica as an Efficient Catalyst for the Synthesis of Biofuel Additive n-Butyl Levulinate - A. Selva Priya; K. R. Sunaja Devi (BioEnergy Research, 2020)

Sequential treatment of paper mill effluent with modified Fenton oxidation and bioflocculation - Khanindra Sharma; Mihirjyoti Pathak; Suravi Kalita; K. G. Bhattacharyya; Neelotpal Sen Sarma; Arundhuti Devi (Environment, Development and Sustainability, 2020)

Statistical Method of Forecasting of Seasonal Precipitation over the Northwest Himalayas: North Atlantic Oscillation as Precursor - Usha Devi; M. S. Shekhar; G. P. Singh; S. K. Dash (Pure and Applied Geophysics, 2020)

Novel formulations of Bacillus thuringiensis var. kurstaki: an eco-friendly approach for management of lepidopteran pests - P. S. Vimala Devi; P. Duraimurugan; K. S. V. Poorna Chandrika; V. Vineela; P. P. Hari (World Journal of Microbiology and Biotechnology, 2020)

An effective method for extraction of high purity phycocyanins (C-PC and A-PC) from dry biomass of Arthrospira maxima - A. Chandralekha Devi; Hrishikesh A. Tavanandi; K. Govindaraju; K. S. M. S. Raghavarao (Journal of Applied Phycology, 2020)

Thunderstorm dynamics through wind profiling features: the first observation by stratospheric-tropospheric radar of GU - M. Devi; S. Patgiri; A. Medhi; S. Das; M. Saikia; A. K. Barbara; S. S. Kakatkar; K. P. Ray (Natural Hazards, 2020)

Dissipation Kinetics of Hexaconazole and Lambda-Cyhalothrin Residue in Soil and Potato Plant - Raginee Devi; R. P. Singh; A. K. Sachan (Potato Research, 2019)

Strong motion generation area modelling of the 2008 Iwate earthquake, Japan using modified semi-empirical technique - Sandeep; A Joshi; Sonia Devi; Parveen Kumar; S K Sah; Sohan Lal; Kamal (Journal of Earth System Science, 2019)

Modeling of 2011 IndoNepal Earthquake and Scenario Earthquakes in the Kumaon Region and Comparative Attenuation Study Using PGA Distribution with the Garhwal Region - Sandeep; A. Joshi; S. K. Sah; Parveen Kumar; Sohan Lal; Sonia Devi; Monika (Pure and Applied Geophysics, 2019)

Transverse Tectonics Structures in the Garhwal Himalaya Corridor Inferred from 3D Inversion of Magnetotelluric Profile Data - Anita Devi; Mohammad Israil; Pravin K. Gupta; S. K. Varshney; Naser Meqbel (Pure and Applied Geophysics, 2019)

Gene Expression Profiling in Sugarcane Genotypes During Drought Stress and Rehydration - K. Devi; P. T. Prathima; R. Gomathi; R. Manimekalai; K. Lakshmi; A. Selvi (Sugar Tech, 2019)

New Records of Two Brachyuran Crabs (Crustacea: Decapoda), Naxioides robillardi (Miers, 1882) (Epialtidae) and Lupocyclus tugelae Barnard, 1950 (Portunidae) from India - Suvarna S. Devi; Appukuttannair Biju Kumar; Peter K. L. Ng (Thalassas: An International Journal of Marine Sciences, 2019)

PHD-2 activation: a novel strategy to control HIF-1α and mitochondrial stress to modulate mammary gland pathophysiology in ER+ subtype - Uma Devi; Manjari Singh; Subhadeep Roy; Avinash C. Tripathi; Pushpraj S. Gupta; Shailendra K. Saraf; Md. Nazam Ansari; Abdulaziz S. Saeedan; Gaurav Kaithwas (Naunyn-Schmiedeberg's Archives of Pharmacology, 2019)

Effectiveness of Field Water Tube for Standardization of Alternate Wetting and Drying (AWD) Method of Water Management in Lowland Rice ( Oryza Sativa L.) - Mote Kishor Jalindar; V. Praveen Rao; V. Ramulu; K. Avil Kumar; M. Uma Devi (Irrigation and Drainage, 2019)
A field study was conducted to discover the effectiveness of a field water tube as a practical indicator for water management in lowland rice ( Oryza sativa L.). The field water tube was of 40 cm length and 15 cm in diameter so that the groundwater table could be easily visible. This tube with perforations was inserted into the ground until 20 cm protruded above soil level. It enabled monitoring of the water level inside the tube as and when the ponded water level drops to a certain permissible level, i.e. 5–15 cm‐surface. Practical indicators used in the experiment to find out the effectiveness of the field water tube were water stress parameters, viz. soil penetration resistance, soil crack width, soil siltation depth and days needed for ponded water to drop to a designated level in the field water tube. Field trials revealed that with 5 cm submergence depth and a threshold of 5 or 10 cm water depth below the ground level in the field the water tube was found to be a safe alternate wetting and drying practice in view of the higher yield (7060–7210 kg ha −1 ), considerable water saving (26.6–35.0%) and higher water productivity (1.15–1.27 kg m −3 ). © 2019 John Wiley & Sons, Ltd.

Orange-fleshed cucumber (Cucumis sativus var. sativus L.) germplasm from North-East India: agro-morphological, biochemical and evolutionary studies - Pragya Ranjan; Anjula Pandey; A. D. Munshi; Rakesh Bhardwaj; K. K. Gangopadhyay; Pavan Kumar Malav; Chithra Devi Pandey; K. Pradheep; B. S. Tomar; Ashok Kumar (Genetic Resources and Crop Evolution, 2019)

Transformation of waste tin-plated steel to iron nanosheets and their application in generation of oxygen - M. M. Devi; K. N. Ojha; A. K. Ganguli; M. Jha (International Journal of Environmental Science and Technology, 2019)

Deciphering species relationships and evolution in Chenopodium through sequence variations in nuclear internal transcribed spacer region and amplified fragment-length polymorphism in nuclear DNA - Nikhil K. Chrungoo; Rajkumari Jashmi Devi; Shailendra Goel; Kamal Das (Journal of Genetics, 2019)

First report of Lasiodiplodia theobromae associated with stem-end rot of mango in Manipur, India - Rahee Bui; Bireswar Sinha; Ph. Sobita Devi; K. Dinesh; R. K. Dilip (Indian Phytopathology, 2018)

Role of enhanced synoptic activity and its interaction with intra-seasonal oscillations on the lower extended range prediction skill during 2015 monsoon season - S. Abhilash; R. Mandal; A. Dey; R. Phani; S. Joseph; R. Chattopadhyay; S. De; N. K. Agarwal; A. K. Sahai; S. Sunitha Devi; M. Rajeevan (Climate Dynamics, 2018)

Variability of Diurnal Temperature Range During Winter Over Western Himalaya: Range- and Altitude-Wise Study - M. S. Shekhar; Usha Devi; S. K. Dash; G. P. Singh; Amreek Singh (Pure and Applied Geophysics, 2018)

Effect of early natal supplementation of paracetamol on attenuation of exotoxin/endotoxin induced pyrexia and precipitation of autistic like features in albino rats - Abdulaziz S. Saeedan; Indu Singh; Mohd. Nazam Ansari; Manjari Singh; Jitendra K. Rawat; Uma Devi; Swetlana Gautam; Rajnish K. Yadav; Gaurav Kaithwas (Inflammopharmacology, 2018)

Simultaneous quantitative monitoring of four indicator contaminants of emerging concern (CEC) in different water sources of Central India using SPE/LC-(ESI)MS-MS - Roshan Appa; V. A. Mhaisalkar; Amit Bafana; S. Saravana Devi; Kannan Krishnamurthi; Tapan Chakrabarti; Pravin K. Naoghare (Environmental Monitoring and Assessment, 2018)

Genome-Wide Analysis in Wild and Cultivated Oryza Species Reveals Abundance of NBS Genes in Progenitors of Cultivated Rice - Hukam C. Rawal; S. V. Amitha Mithra; Kirti Arora; Vishesh Kumar; Neha Goel; Dwijesh Chandra Mishra; K. K. Chaturvedi; Anil Rai; S. Vimala Devi; T. R. Sharma; Amolkumar U. Solanke (Plant Molecular Biology Reporter, 2018)

Phenazine‐1‐carboxylic acid and soil moisture influence biofilm development and turnover of rhizobacterial biomass on wheat root surfaces - Melissa K. LeTourneau; Matthew J. Marshall; John B. Cliff; Robert F. Bonsall; Alice C. Dohnalkova; Dmitri V. Mavrodi; S. Indira Devi; Olga V. Mavrodi; James B. Harsh; David M. Weller; Linda S. Thomashow (Environmental Microbiology, 2018)
Summary Phenazine‐1‐carboxylic acid (PCA) is produced by rhizobacteria in dryland but not in irrigated wheat fields of the Pacific Northwest, USA. PCA promotes biofilm development in bacterial cultures and bacterial colonization of wheat rhizospheres. However, its impact upon biofilm development has not been demonstrated in the rhizosphere, where biofilms influence terrestrial carbon and nitrogen cycles with ramifications for crop and soil health. Furthermore, the relationships between soil moisture and the rates of PCA biosynthesis and degradation have not been established. In this study, expression of PCA biosynthesis genes was upregulated relative to background transcription, and persistence of PCA was slightly decreased in dryland relative to irrigated wheat rhizospheres. Biofilms in dryland rhizospheres inoculated with the PCA‐producing (PCA + ) strain Pseudomonas synxantha 2‐79RN 10 were more robust than those in rhizospheres inoculated with an isogenic PCA‐deficient (PCA ‐ ) mutant strain. This trend was reversed in irrigated rhizospheres. In dryland PCA + rhizospheres, the turnover of 15 N‐labelled rhizobacterial biomass was slower than in the PCA ‐ and irrigated PCA + treatments, and incorporation of bacterial 15 N into root cell walls was observed in multiple treatments. These results indicate that PCA promotes biofilm development in dryland rhizospheres, and likely influences crop nutrition and soil health in dryland wheat fields.

Standardization of Alternate Wetting and Drying (AWD) Method of Water Management in Lowland Rice ( ORYZA Sativa L.) for Upscaling in Command Outlets - Kishor Mote; V. Praveen Rao; V. Ramulu; K. Avil Kumar; M. Uma Devi (Irrigation and Drainage, 2018)
The experiment was conducted in irrigated lowlands and followed alternate wetting and drying (AWD) practices by using field water tubes. The site had sandy clay soil. Grain yield was 6.0–7.2 t ha −1 with AWD irrigation and 7.5 t ha −1 with continuous submergence irrigation. Non‐significant ( P > 0.05) difference was registered in yield attributes and grain yield between continuous submergence of irrigation and I 5 (AWD irrigation regime of 5 cm submergence depth from 15 DAT (days after transplanting) to physiological maturity when the ponded water level drops to 5 cm below ground level) and I 6 (AWD irrigation regime of 5 cm submergence depth from 15 DAT to physiological maturity when the ponded water level drops to 10 cm below ground level). There was a decrease in yield attributes and grain yield with the I 4 (AWD irrigation regime of 3 cm submergence depth from 15 DAT to physiological maturity when the ponded water level drops to 15 cm below ground level). Of various irrigation regimes, AWD irrigation regimes of I 5 ( 57 900 ha −1 ) and I 6 ( 56 500 ha −1 ) registered higher net returns with a B: C ratio of 1.27 and 1.29, respectively, owing to higher grain yield coupled with lower application of water. Copyright © 2017 John Wiley & Sons, Ltd.

Persistence, dissipation and consumer risk assessment of a combination formulation of flubendiamide and deltamethrin on cucumber - K.K. Sharma; V. Shashi Bhushan; Cherukuri Sreenivasa Rao; K. Narsimha Reddy; Hemanta Banerjee; Swagata Mandal; Balwinder Singh; R.S. Battu; Gagan Jyot; S.K. Sahoo; Soudamini Mohapatra; S. Lekha; et al. (Food Additives & Contaminants: Part A, 2018)

Progress in somatic hybridization research in potato during the past 40 years - Jagesh Kumar Tiwari; Sapna Devi; Nilofer Ali; Satish K. Luthra; Vinod Kumar; Vinay Bhardwaj; Rajesh K. Singh; Shashi Rawat; Swarup K. Chakrabarti (Plant Cell, Tissue and Organ Culture (PCTOC), 2018)

Effects of Water pH on Life History Parameters of a New Bosminid Cladocera: Bosmina (Bosmina) Tripurae (Korinek, Saha and Bhattachaya, 1999) in Laboratory Condition - Himadri Saha; K. S. Wisdom; Asem Lembika Devi; Da-u-ruhi Pde; Sukham Tuni Devi; Makamguang Kamei; Anamika Biswas; Ratan K. Saha; Prasenjit Pal (Bulletin of Environmental Contamination and Toxicology, 2017)

Comparative efficacy of alpha-linolenic acid and gamma-linolenic acid to attenuate valproic acid-induced autism-like features - Sneha Yadav; Virendra Tiwari; Manjari Singh; Rajnish K. Yadav; Subhadeep Roy; Uma Devi; Swetlana Gautam; Jitendra Kumar Rawat; Mohd. Nazam Ansari; Abdulaziz Sa Saeedan; Anand Prakash; Shubhini A. Saraf; et al. (Journal of Physiology and Biochemistry, 2017)

The origin of DCs and capacity for immunologic tolerance in central and peripheral tissues - K . Sanjana P. Devi; Niroshana Anandasabapathy (Seminars in Immunopathology, 2017)

Developing a biosorbent from Aegle Marmelos leaves for removal of methylene blue from water - S. Baruah; A. Devi; K. G. Bhattacharyya; A. Sarma (International Journal of Environmental Science and Technology, 2017)

Foraminifera of Lakshadweep Archipelago, Arabian Sea - Subhadra Devi Gadi; P. Vidya; M. S. Mustak; K. P. Rajashekhar (Proceedings of the Zoological Society, 2016)

Improvement in performance of sludge-based adsorbents by controlling key parameters by activation/modification: A critical review - Parmila Devi; Anil K. Saroha (Critical Reviews in Environmental Science and Technology, 2016)

Studies on Photocleavage, DNA Binding, Cytotoxicity, and Docking Studies of Ruthenium(II) Mixed Ligand Complexes - Yata Praveen Kumar; C. Shobha Devi; A. Srishailam; N. Deepika; V. Ravi Kumar; P. Venkat Reddy; K Nagasuryaprasad; Surya S. Singh; Penumaka Nagababu; S. Satyanarayana (Journal of Fluorescence, 2016)

Risk assessment and technical feasibility of usage of paper mill sludge biochar-based exhausted adsorbent for geopolymeric brick formation - Parmila Devi; Anil K. Saroha (Environmental Science and Pollution Research, 2016)

α-Chymotrypsin regulates free fatty acids and UCHL-1 to ameliorate N-methyl nitrosourea induced mammary gland carcinoma in albino wistar rats - Asha Rani; Subhadeep Roy; Manjari Singh; Uma Devi; Rajnish K. Yadav; Swetlana Gautam; Jitendra K. Rawat; Mohd. Nazam Ansari; Abdulaziz S. Saeedan; Anand Prakash; Gaurav Kaithwas (Inflammopharmacology, 2016)

Redefining the role of peripheral LPS as a neuroinflammatory agent and evaluating the role of hydrogen sulphide through metformin intervention - Virendra Tiwari; Manjari Singh; Jitendra K. Rawat; Uma Devi; Rajnish K. Yadav; Subhadeep Roy; Swetlana Gautam; Shubhini A. Saraf; Vikas Kumar; Nazam Ansari; Abdulaziz S. Saeedan; Gaurav Kaithwas (Inflammopharmacology, 2016)

Copper transporters and chaperones: Their function on angiogenesis and cellular signalling - S R Bharathi Devi; Aloysius Dhivya M; K N Sulochana (Journal of Biosciences, 2016)

Identification and validation of novel alleles of rice blast resistant gene Pi54, and analysis of their nucleotide diversity in landraces and wild Oryza species - G. Ramkumar; M. S. Madhav; S. J. S. Rama Devi; B. Umakanth; M. K. Pandey; M. S. Prasad; R. M. Sundaram; B. C. Viraktamath; V. Ravindra Babu (Euphytica, 2016)

Application of Glass Transition in Food Processing - S. Balasubramanian; Apramita Devi; K. K. Singh; S. J. D Bosco; Ashish M. Mohite (Critical Reviews in Food Science and Nutrition, 2016)

Field level evaluation of rice introgression lines for heat tolerance and validation of markers linked to spikelet fertility - V. Vishnu Prasanth; Kumari Ramana Basava; M. Suchandranath Babu; Venkata Tripura V.G.N.; S. J. S. Rama Devi; S. K. Mangrauthia; S. R. Voleti; N. Sarla (Physiology and Molecular Biology of Plants, 2016)

Design and development of oxobenzimidazoles as novel androgen receptor antagonists - R. Elancheran; K. Saravanan; Bhaswati Choudhury; S. Divakar; S. Kabilan; M. Ramanathan; Babulal Das; R. Devi; Jibon Kotoky (Medicinal Chemistry Research, 2016)

Detection and molecular characterization of astroviruses in turkeys - Azad Singh; Sunil K. Mor; Naresh Jindal; Devi Patnayak; Nader M. Sobhy; Nhungoc Ti Luong; Sagar M. Goyal (Archives of Virology, 2016)

Monitoring adventitious presence of transgenes in ex situ okra (Abelmoschus esculentus) collections conserved in genebank: a case study - Rakesh Kumar Bairwa; Monika Singh; Rajesh K. Bhoge; Chitra Devi; Gurinderjit Randhawa (Genetic Resources and Crop Evolution, 2016)

Heavy metal content in various types of candies and their daily dietary intake by children - Parmila Devi; Vandana Bajala; V. K. Garg; Suman Mor; Khaiwal Ravindra (Environmental Monitoring and Assessment, 2016)

Dual Drug Delivery Using Lactic Acid Conjugated SLN for Effective Management of Neurocysticercosis - Rekha Devi; Ankit Jain; Pooja Hurkat; Sanjay K. Jain (Pharmaceutical Research, 2015)

Influence of Processing Variables and Storage on the Fruit Drink Developed from Taktir; Wild Fruit of Himalaya - P. Suresh Kumar; V. K. Choudhary; P. Devi; M. Kanwat; A. Sangeetha (Proceedings of the National Academy of Sciences, India Section B: Biological Sciences, 2015)

Expression and inheritance of chimeric cry2AX1 gene in transgenic cotton plants generated through somatic embryogenesis - A. R. Sakthi; A. Naveenkumar; P. S. Deepikha; N. Balakrishnan; K. K. Kumar; E. Kokila Devi; V. Balasubramani; L. Arul; P. K. Singh; D. Sudhakar; V. Udayasuriyan; P. Balasubramanian (In Vitro Cellular & Developmental Biology - Plant, 2015)

Erratum to: Unique miRNome during anthesis in drought-tolerant indica rice var. Nagina 22 - Shivani Kansal; Roseeta Devi Mutum; Sonia C. Balyan; Mukesh K. Arora; Ashok Kumar Singh; Saloni Mathur; Saurabh Raghuvanshi (Planta, 2015)

Response of micro- and mesozooplankton in the southwestern Bay of Bengal to a cyclonic eddy during the winter monsoon, 2005 - K. J. Jayalakshmi; P. Sabu; C. R. Asha Devi; V. N. Sanjeevan (Environmental Monitoring and Assessment, 2015)

Unique miRNome during anthesis in drought-tolerant indica rice var. Nagina 22 - Shivani Kansal; Roseeta M. Devi; Sonia C. Balyan; Mukesh K. Arora; Anil K. Singh; Saloni Mathur; Saurabh Raghuvanshi (Planta, 2015)

Late Pleistocene palaeoclimate based on vegetation of the Eastern Himalayan foothills in the Indo-Burma Range, India - Sadhan K. Basumatary; Swati Tripathi; Samir K. Bera; Chandra Mohan Nautiyal; Nilakshee Devi; Gajen Chandra Sarma (Palynology, 2015)

Variations in Physiological Response, Lipid Peroxidation, Antioxidant Enzyme Activities, Proline and Isoflavones Content in Soybean Varieties Subjected to Drought Stress - M. K. Akitha Devi; P. Giridhar (Proceedings of the National Academy of Sciences, India Section B: Biological Sciences, 2015)

New insights of superoxide dismutase inhibition of pyrogallol autoxidation - T. Ramasarma; Aparna V. S. Rao; M. Maya Devi; R. V. Omkumar; K. S. Bhagyashree; S. V. Bhat (Molecular and Cellular Biochemistry, 2015)

A Case Report of a 14 Year Old Male with Pseudohypoparathyroidism Associated with Multiple Hormonal Resistance - Prasanthi Mannava; Afshan Masood; Ambika K. Devi (Indian Journal of Clinical Biochemistry, 2015)

Prevalence of peste des petits ruminants in goats in North-East India - V. Balamurugan; Sutopa Das; D. S. N. Raju; Indirani Chakravarty; M. Nagalingam; D. Hemadri; G. Govindaraj; N. Ibotombi Singh; Keduzol Ltu; Maitryee Devi; K. Sharma; M. R. Gajendragad; et al. (VirusDisease, 2014)

Persistence and risk assessment of spiromesifen on tomato in India: a multilocational study - K. K. Sharma; Irani Mukherjee; Balwinder Singh; Kousik Mandal; Sanjay K. Sahoo; Hemanta Banerjee; Tirthankar Banerjee; Sankhajit Roy; Paresh G. Shah; Hemlatta K. Patel; Anil R. Patel; S. Naseema Beevi; et al. (Environmental Monitoring and Assessment, 2014)

Residual behavior and risk assessment of flubendiamide on tomato at different agro-climatic conditions in India - K. K. Sharma; Irani Mukherjee; Balwinder Singh; Sanjay K. Sahoo; N. S. Parihar; B. N. Sharma; V. D. Kale; R. V. Nakat; A. R. Walunj; Saudamini Mohapatra; A. K. Ahuja; Debi Sharma; et al. (Environmental Monitoring and Assessment, 2014)

Cadmium and copper toxicity in three marine macroalgae: evaluation of the biochemical responses and DNA damage - M. Yokesh Babu; L. Palanikumar; N. Nagarani; V. Janaki Devi; S. Ramesh Kumar; C. M. Ramakritinan; A. K. Kumaraguru (Environmental Science and Pollution Research, 2014)

A comparative study on mesozooplankton abundance and diversity between a protected and an unprotected coastal area of Andaman Islands - Honey U. K. Pillai; K. V. Jayalakshmy; A. Biju; K. J. Jayalakshmi; V. T. Paulinose; C. B. L. Devi; V. R. Nair; C. Revichandran; N. R. Menon; C. T. Achuthankutty; S. U. Panampunnayil (Environmental Monitoring and Assessment, 2014)

Safety evaluation of flubendiamide and its metabolites on cabbage and persistence in soil in different agroclimatic zones of India - K. K. Sharma; Saudamini Mohapatra; A. K. Ahuja; M. Deepa; Debi Sharma; G. K. Jagdish; N. Rashmi; R. S. Battu; S. K. Sharma; Balwinder Singh; N. S. Parihar; B. N. Sharma; et al. (Environmental Monitoring and Assessment, 2014)

Safety and toxicological evaluation of Rhizopora mucronata (a mangrove from Vellar estuary, India): assessment of mutagenicity, genotoxicity and in vivo acute toxicity - N. Suganthy; K. Karthikeyan; G. Archunan; S. Karutha Pandian; K. Pandima Devi (Molecular Biology Reports, 2014)

Assessment of coastal dune characteristics using georadar imaging and sedimentological analysis: Odisha and Visakhapatnam, India - K. Devi; M. C. Raicy; Deshraj Trivedi; P. Srinivasan; S. G. N. Murthy; Ronald J. Goble; Rajesh R. Nair (Journal of Coastal Conservation, 2013)

Synthesis and biological evaluation of 1-(3-chloro-2-oxo-4-phenylazetidin-1-yl)-3-(2-oxo-2-(10H-phenothiazin-10-yl)ethyl)urea derivatives - A. Rajasekaran; K. Sheeja Devi (Medicinal Chemistry Research, 2013)

Fungal biodegradation of phthalate plasticizer in situ - S. Pradeep; P. Faseela; M. K. Sarath Josh; S. Balachandran; R. Sudha Devi; Sailas Benjamin (Biodegradation, 2013)

Integrated approach of assessing sedimentary characteristics of onshore sand deposits on the Velankanni coast, Tamil Nadu, India: sheds light on extreme wave event signatures - K. Devi; C. S. Vijaya Lakshmi; M. C. Raicy; P. Srinivasan; S. G. N. Murthy; S. M. Hussain; Ilya Buynevich; Rajesh R. Nair (Journal of Coastal Conservation, 2013)

Effect of exogenous lead on growth and carbon metabolism of pea (Pisum sativum L) seedlings - Rachana Devi; Nidhi Munjral; Anil K Gupta; Narinder Kaur (Physiology and Molecular Biology of Plants, 2013)

Cellular alterations and modulation of protein expression in bitumen-challenged human osteoblast cells - Alka Dhondge; Subin Surendran; Muhil Vannan Seralathan; Pravin K. Naoghare; Kannan Krishnamurthi; Sivanesan Saravana Devi; Tapan Chakrabarti (Environmental Science and Pollution Research, 2012)

Over-the-Horizon Anomalous VHF Propagation and Earthquake Precursors - M. Devi; A. K. Barbara; Ya. Yu. Ruzhin; M. Hayakawa (Surveys in Geophysics, 2012)

Application of a Chimeric Protein Construct having Enterotoxin B and Toxic Shock Syndrome Toxin Domains of S. aureus in Immunodiagnostics - R. Shylaja; Devi Kalyan Kumar Thakasi; H. S. Murali; K. Prakash Narayana Reddy; H. V. Batra (Indian Journal of Microbiology, 2012)

Phenotypic and genetic characterization of Vibrio cholerae O1 clinical isolates collected through national antimicrobial resistance surveillance network in Nepal - Geeta Shakya; Dong Wook Kim; John D. Clemens; Sarala Malla; Bishnu Prasad Upadhyaya; Shyam Prakash Dumre; Sirjana Devi Shrestha; Shailaja Adhikari; Supriya Sharma; Nisha Rijal; Sanjaya K. Shrestha; Carl Mason; et al. (World Journal of Microbiology and Biotechnology, 2012)

MMP 9 Gene Promoter Polymorphism in Gastric Cancer - D. Krishnaveni; Amar Chand Bhayal; K. Sri Manjari; A. Vidyasagar; M. Uma Devi; M. Ramanna; A. Jyothy; Pratibha Nallari; A. Venkateshwari (Indian Journal of Clinical Biochemistry, 2012)

Lower Oligocene bivalves of Ramanian Stage from Kachchh, Gujarat, India - R P Kachhara; R L Jodhawat; K Bigyapati Devi (Journal of Earth System Science, 2012)

Kamlet-Taft and Catalan Studies of Some Novel Y-Shaped Imidazole Derivatives - J. Jayabharathi; V. Thanikachalam; K. Brindha Devi; M. Venkatesh Perumal (Journal of Fluorescence, 2012)

Gene variants of XRCC4 and XRCC3 and their association with risk for urothelial bladder cancer - Rama Devi Mittal; Ruchika Gangwar; Raju K. Mandal; Priyanka Srivastava; Dinesh K. Ahirwar (Molecular Biology Reports, 2012)

High Performance Thin Layer Chromatography (HPTLC) profile of an insecticidal compound of Trochus radiatus and assessment of mucus-associated bacterial extracts - Mary Elizabeth K. Gnanambal; K. C. Ramya Devi; P. Hareesh Chandra; Edward J. K. Patterson (Phytoparasitica, 2011)

Heterosis, molecular diversity, combining ability and their interrelationships in short duration maize (Zea mays L.) across the environments - Pooja Devi; N. K. Singh (Euphytica, 2011)

Application of GIS for Evaluation and Design of Watershed Guidelines - R. S. Bhalla; Neil W. Pelkey; K. V. Devi Prasad (Water Resources Management, 2011)

Screening of Rhizobacteria for Their Plant Growth Promotion Ability and Antagonism Against Damping off and Root Rot Diseases of Broad Bean (Vicia faba L.) - S. Indira Devi; N. C. Talukdar; K. Chandradev Sharma; K. Jeyaram; M. Rohinikumar (Indian Journal of Microbiology, 2011)

Economic analysis of risk of gastrointestinal parasitic infection in cattle in North Eastern States of India - S. Bandyopadhyay; S. Mandal; K. K. Datta; P. Devi; S. De; A. K. Bera; D. Bhattacharya (Tropical Animal Health and Production, 2010)

Green fluorescent protein as a visual selection marker for coffee transformation - Manoj K. Mishra; Santosini Devi; Alex McCormac; Nigel Scott; DongFang Chen; Malcolm Elliott; Adrian Slater (Biologia, 2010)

Anomalous total electron content (TEC) and atmospheric refractivity prior to the very strong China earthquake of May 2008 - M. Devi; A. K. Barbara; A. H. Depueva; Y. Y. Ruzhin; V. Depuev (International Journal of Remote Sensing, 2010)

Acclimatory response to hydrogen peroxide and glutathione under salt-boron stress through their impact on mineral nutrition and antioxidant defense system in pigeonpea (Cajanus cajan L.) - S. Chawla; S. C. Goyal; Rajiv Angrish; C. Rani; V. Arora; K. S. Datta; S. Madaan; S. Devi (Physiology and Molecular Biology of Plants, 2010)

Hypocalcemia in Pregnant Women - Ashok Kumar; Krishna Agarwal; Salam G. Devi; Ram K. Gupta; Swaraj Batra (Biological Trace Element Research, 2010)

Sarcoptic mange infestation in pigs in a hilly region of Meghalaya - M. Das; R. Laha; P. Devi; R. K. Bordoloi; S. Naskar (Tropical Animal Health and Production, 2010)

Strain analysis and stratigraphic status of Nongkhya, Sumer and Mawmaram conglomerates of Shillong basin, Meghalaya, India - Niva Rani Devi; K. P. Sarma (Journal of Earth System Science, 2010)

Polymorphisms in the vitamin D receptor and the androgen receptor gene associated with the risk of urolithiasis - Rama Devi Mittal; D. K. Mishra; P. Srivastava; P. Manchanda; H. K. Bid; R. Kapoor (Indian Journal of Clinical Biochemistry, 2010)

Multiplex PCR for identification of parasitic eggs of Oesophagostomum spp. Isolated from sheep and goat - S. Bandyopadhyay; S. Naskar; P. Devi; A. K. Bera; S. De; D. Pan; T. Rana; S. Das; S. Sikdar; D. Bhattacharya (Proceedings of the Zoological Society, 2009)

A limited innate immune response is induced by a replication-defective herpes simplex virus vector following delivery to the murine central nervous system - Zane Zeier; J Santiago Aguilar; Cecilia M Lopez; GB Devi-Rao; Zachary L Watson; Henry V Baker; Edward K Wagner; David C Bloom (Journal of NeuroVirology, 2009)

Antibiotic resistance and plasmid profiling of Vibrio parahaemolyticus isolated from shrimp farms along the southwest coast of India - Rekha Devi; P. K. Surendran; K. Chakraborty (World Journal of Microbiology and Biotechnology, 2009)

Genotoxicity of sludges, wastewater and effluents from three different industries - K. Krishnamurthi; S. Saravana Devi; J. G. Hengstler; Matthias Hermes; Koel Kumar; Dipanwita Dutta; S. Muhil Vannan; T. S. Subin; R. R. Yadav; T. Chakrabarti (Archives of Toxicology, 2008)

Evaluation of in vitro antimicrobial activity of leaf and stem essential oils of Chloroxylon swietenia DC. - S. Ravi Kiran; P. Sita Devi; K. Janardhan Reddy (World Journal of Microbiology and Biotechnology, 2008)

Temporal characteristics of aerosol physical properties at Visakhapatnam on the east coast of India during ICARB — Signatures of transport onto Bay of Bengal - K. Niranjan; V. Sreekanth; B. L. Madhavan; T. Anjana Devi; B. Spandana (Journal of Earth System Science, 2008)

Molecular characterization of reciprocal crosses of Aerides vandarum and Vanda stangeana (Orchidaceae) at the protocorm stage - Rajkumar Kishor; H. S. Devi; K. Jeyaram; M. R. K. Singh (Plant Biotechnology Reports, 2008)

Remote sensing and GIS application for land quality assessment for coffee growing areas of Karnataka - G. M. Shalima Devi; K. S. Anil Kumar (Journal of the Indian Society of Remote Sensing, 2008)

Stress-inducible expression of At DREB1A in transgenic peanut (Arachis hypogaea L.) increases transpiration efficiency under water-limiting conditions - Pooja Bhatnagar-Mathur; M. Jyostna Devi; D. Srinivas Reddy; M. Lavanya; Vincent Vadez; R. Serraj; K. Yamaguchi-Shinozaki; Kiran K. Sharma (Plant Cell Reports, 2007)

Identification of a high frequency of chromosomal rearrangements in the centromeric regions of prostate cancer patients - V. Balachandar; B. Lakshman Kumar; K. Sasikala; P. Manikantan; R. Sangeetha; S. Mohana Devi (Journal of Zhejiang University-SCIENCE B, 2007)

Isolation of steroidal glycosides from Solanum xanthocarpum and studies on their antifungal activities - Okram M. Singh; K. Subharani; N. I. Singh; N. Babita Devi; L. Nevidita (Natural Product Research, 2007)

Hydrogen Cyanide-Producing Rhizobacteria Kill Subterranean Termite Odontotermes obesus (Rambur) by Cyanide Poisoning Under In Vitro Conditions - K. Kanchana Devi; Nidhi Seth; Shalini Kothamasi; David Kothamasi (Current Microbiology, 2007)

Rice can acclimate to lethal level of salinity by pretreatment with sublethal level of salinity through osmotic adjustment - M. Djanaguiraman; J. Annie Sheeba; Arun K. Shanker; D. Durga Devi; U. Bangarusamy (Plant and Soil, 2006)

Allee Effect in the Infection Dynamics of the Entomopathogenic Fungus Beauveria bassiana (Bals) Vuill. on the Beetle, Mylabris pustulata - K. Uma Devi; C. Uma Maheswara Rao (Mycopathologia, 2006)

Selenium – an antioxidative protectant in soybean during senescence - M. Djanaguiraman; D. Durga Devi; Arun K. Shanker; J. Annie Sheeba; U. Bangarusamy (Plant and Soil, 2005)

Protective effect of Premna tomentosa extract (L. verbanacae) on acetaminophen-induced mitochondrial dysfunction in rats - K. Pandima Devi; M. Sreepriya; K. Balakrishna; T. Devaki (Molecular and Cellular Biochemistry, 2005)

Altered structure and expression of RB1 gene and increased phosphorylation of pRb in human vestibular schwannomas - R. Thomas; P. D. Antony Herold Prabhu; J. Mathivanan; Rohini; D. Sivakumar; P. N. Jayakumar; B. Indira Devi; S. Satish; K. V. R. Sastry; R. Gope (Molecular and Cellular Biochemistry, 2005)

Cholinesterase Activity in Clam Meretrix casta: Possible Biomarker for Organophosphate Pesticide Pollution - K. P. Devi; S. K. Pandian; N. S. S. Kumar (Bulletin of Environmental Contamination and Toxicology, 2005)

Identification of Virulent Isolates of the Entomopathogenic Fungus Nomuraea Rileyi (F) Samson for the Management of Helicoverpa Armigera and Spodoptera Litura - P.S. Vimala Devi; Y.G. Prasad; D. Anitha Chowdary; L. Mallikarjuna Rao; K. Balakrishnan (Mycopathologia, 2003)

The optimum and tolerance pH range is correlated to colonial morphology in isolates of the entomopathogenic fungus Beauveria bassiana – a potential biopesticide - J. Padmavathi; K. Uma Devi; C. Uma Maheswara Rao (World Journal of Microbiology and Biotechnology, 2003)

An efficient protocol for shoot regeneration and genetic transformation of pigeonpea [Cajanus cajan (L.) Millsp.] using leaf explants - S. Dayal; M. Lavanya; P. Devi; K. K. Sharma (Plant Cell Reports, 2003)

Effect of time of nitrogen application on yield and quality of early maturing sugarcane varieties under rainfed conditions - M. Bharatha Lakshmi; T. Chitkala Devi; I. V. Narasimha Rao; K. L. Rao (Sugar Tech, 2003)

The Downstream Activation Sequence of the Strict Late Herpes Simplex Virus Type 1 UL38 Promoter Interacts With hTAFII70, a Component of TFIID - Matthew D. Petroski; Gayathri B. Devi-Rao; Marcia K. Rice; Edward K. Wagner (Virus Genes, 2001)

Immunomodulation of excretory secretory materials from the filarial parasiteSetaria digitata - R. Kaleysa Raj; C. G. Pradeep; C. Maya Devi; Linda John; M. R. Rekha; Sheeba K. Oommen (Indian Journal of Clinical Biochemistry, 1997)

Timing of N fertilization on N2 fixation, N recovery and soil profile nitrate dynamics on sorghum/pigeonpea intercrops on Alfisols on the semi-arid tropics - Joseph J. Adu-Gyamfi; O. Ito; T. Yoneyama; Gayatri Devi; K. Katayama (Nutrient Cycling in Agroecosystems, 1997)